Resin composition and method for producing same, and plasticized starch and method for producing same
The resin composition, featuring plasticized starch and a thermoplastic resin, addresses the challenges of reducing starch granule size and preventing additive bleed in plastic molded products, resulting in improved moldability and physical properties.
Patent Information
- Application Number
- JP2021014174
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-10
- Filing Date
- 2021-02-01
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2041-02-01
AI Technical Summary
Conventional starch-based polymer materials in plastic molded products face challenges in reducing starch granule size, achieving good molding processability, and preventing additive bleed under high temperature and humidity conditions.
A resin composition comprising plasticized starch material, a thermoplastic resin, and a polar organic compound capable of gelatinizing or plasticizing starch at temperatures above room temperature, which reduces starch granule size to 2 μm or less and prevents additive bleed.
The solution enables the production of plastic molded articles with improved moldability, physical properties, and surface smoothness, while also preventing additive bleed under high temperature and humidity conditions.
Smart Images

Figure 0007657444000010 
Figure 0007657444000011 
Figure 0007657444000012
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition and a method for producing the same, and to a plasticized starch and a method for producing the same. [Background technology]
[0002] Conventional plastic molded products are difficult to decompose in the natural environment after disposal, and are one of the causes of environmental pollution. In recent years, materials that decompose in the natural environment after disposal have been studied, and as such materials, plastic molded products containing biomass materials have attracted attention. Since the plastic molded products contain biomass materials as a substitute for petroleum-based materials, it is possible to reduce CO2 emitted during combustion. Examples of biomass materials include waste biomass (food waste, livestock excrement, construction waste, waste paper, etc.), unused biomass (non-edible parts of agricultural crops and forest residues, etc.), and resource grains. More specific examples of biomass materials include wood flour, rice straw, bamboo, and old rice.
[0003] Starch, which is abundant in nature and inexpensive, is used as a biomass material. Starch is a so-called carbon neutral material, in that the amount of carbon dioxide emitted when burned is the same as the amount of carbon dioxide absorbed by the original plant (starch) during its growth. However, starch itself is a high molecular weight material, and has poor fluidity during molding when left as starch, and has difficulties in molding processability, so starch that has been given plasticity by various methods is used. Regarding plastic molded products containing starch, for example, Patent Document 1 below discloses an article containing a polymer content, which includes a starch-based polymer material containing a first starch and a second starch, and a polyolefin-based polymer material, and in which the amount of the polymer content that biodegrades after 91 days is greater than the amount of the first starch and the second starch, based on the results of a biomethane potential test performed at a temperature of about 52°C using an inoculum having about 55% by weight of water and about 45% by weight of organic solids. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-521181 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when a starch-based polymer material is used as a biomass material, it is difficult to reduce the size of the starch granules contained in a plastic molded product under certain conditions. If the starch granules cannot be reduced in size, there is a problem that molding is not possible, and a plastic molded product having excellent physical properties cannot be produced. The present invention aims to provide a new means for providing a plastic molded product containing starch granules with a small particle size. Furthermore, the present invention aims to provide a new means for providing a plastic molded product that can suppress the bleeding of various additives present inside to the surface even under high temperature and high humidity conditions. Furthermore, the present invention aims to provide a new means for providing a plastic molded product to which functionality such as a deodorizing function and an odor preventing function has been imparted. [Means for solving the problem]
[0006] The present inventors have found that a specific plasticized starch material can reduce the particle size of starch granules and provide a plastic molded article that can suppress the bleeding out of various additives present inside to the surface even under high temperature and high humidity conditions.
[0007] That is, the present invention provides a resin composition comprising a plasticized starch material and a thermoplastic resin, wherein the plasticized starch material comprises starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and water, and the particle size of starch granules contained in the resin composition is 2 μm or less. The polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature may include at least one polyhydric alcohol. The resin composition may have a glycerin content of 0% by mass or more and 10% by mass or less. The polyhydric alcohol may include at least one of ethylene glycol and propylene glycol. The resin composition may further include an organic acid. The plasticized starch material may be a starch plasticizer or a modified starch plasticizer. The thermoplastic resin may be a polyolefin resin, a polyester resin, a polystyrene resin, or a mixture of these resins. The resin composition may further contain cellulose nanofibers. The resin composition is formed into the shape of a film, a sheet, or a nonwoven fabric. The resin composition is formed into the shape of a film or sheet, and the surface of the film or sheet is coated with a membrane to form a laminate.
[0008] The present invention also provides a plasticized starch having a plasticized starch material containing starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and water. The present invention provides a plasticized starch that does not have expanded portions. The present invention provides a plasticized starch used for producing a plasticized starch-containing resin composition containing starch granules having a particle size of 2 μm or less. The present invention provides a plasticized starch having a hardness of 20 or more on a durometer type D. The present invention provides plasticized starch in the shape of a cylinder (strand) or pellet.
[0009] The present invention provides a method for producing a resin composition, comprising: a first mixing step of mixing starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and water; a plasticized starch preparation step of preparing a plasticized starch by heating the mixture obtained in the first mixing step to plasticize the starch; and a second mixing step of mixing the plasticized starch and a thermoplastic resin to obtain a resin composition containing starch granules having a particle size of 2 μm or less. The present invention provides a method for producing a resin composition, which includes a mixing step of mixing starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, water, and a thermoplastic resin, and a heating step of heating the mixture obtained in the mixing step to plasticize the starch and obtain starch granules having a particle size of 2 μm or less.
[0010] The present invention provides a method for producing plasticized starch, the method comprising: a mixing step of mixing starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and water; and a plasticization step of plasticizing the starch by heating the mixture obtained in the mixing step.
[0011] The present invention further provides the resin composition, which further contains a functional agent. The functional agent may be at least one selected from an antibacterial agent, a deodorant, and an anti-odor agent, either singly or in combination.
[0012] The present invention further provides the plasticized starch as described above, which contains a functional agent.
[0013] The present invention provides the method for producing the resin composition, wherein a functional agent is further mixed in the first mixing step.
[0014] The present invention provides the method for producing the resin composition, wherein a functional agent is further mixed in the mixing step.
[0015] The present invention provides the method for producing the plasticized starch, wherein a functional agent is further mixed in the mixing step. Effect of the Invention
[0016] The present invention can reduce the size of starch granules in a plastic molded article. Furthermore, it can suppress bleeding out from the surface of the plastic molded article even under high temperature and high humidity conditions. Furthermore, the present invention can impart odor eliminating and odor preventing functions to the plastic molded article. The effects of the present invention are not necessarily limited to the effects described herein, and may be any of the effects described in this specification. [Brief description of the drawings]
[0017] [Figure 1] 1 is an electron microscope photograph of a film surface in an example of this embodiment. [Diagram 2] 1 is an electron microscope photograph of the surface of fibers that make up a nonwoven fabric. [Diagram 3] 11 is an electron microscope photograph of a film surface in another example of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiments for carrying out the present invention will be described in detail. Note that the embodiments described below are representative examples of the present invention, and the present invention is not limited to these embodiments.
[0019] 1.Resin composition
[0020] The resin composition of the present invention comprises a plasticized starch material and a thermoplastic resin, the plasticized starch material comprises starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and water, and the particle size of the starch granules contained in the resin composition is 2 μm or less.
[0021] The resin composition of the present invention may contain the plasticized starch material and the thermoplastic resin in a ratio of, for example, preferably 5 parts by mass:95 parts by mass to 75 parts by mass:25 parts by mass, more preferably 10 parts by mass:90 parts by mass to 70 parts by mass:30 parts by mass, and even more preferably 15 parts by mass:75 parts by mass to 70 parts by mass:30 parts by mass. The resin composition having such a ratio can reduce the size of starch granules contained in a plastic molded article.
[0022] The starch constituting the plasticized starch material is plasticized. This makes it possible to smooth the surface of a molded article formed from the resin composition. In addition, for example, the physical properties (e.g., tensile elongation, etc.) of a film or sheet formed from the resin composition, or the physical properties of a nonwoven fabric can be improved.
[0023] Furthermore, by using the plasticized starch material, molded products (e.g., films and sheets, nonwoven fabrics, etc.) having good quality (e.g., surface smoothness, low coloration, and low odor) can be produced. For example, since the particle size of the starch granules contained in the resin composition of the present invention is 2 μm or less, even if a thin film or sheet or nonwoven fabric is formed from the resin composition, the shape of the starch granules does not appear on the surface. For example, even if the starch content of the resin composition of the present invention is increased, the film or sheet or nonwoven fabric formed from the resin composition does not have the shape of starch granules on its surface.
[0024] In addition, the inclusion of the plasticized starch material in the resin composition of the present invention can impart transparency to the resin composition and molded articles (e.g., films or sheets, nonwoven fabrics) formed from the resin composition. In addition, the inclusion of the plasticized starch material in the resin composition of the present invention can smooth the surfaces of the resin composition and molded articles (e.g., films or sheets, nonwoven fabrics) formed from the resin composition.
[0025] The resin composition of the present invention contains the plasticized starch material and the thermoplastic resin as main components. The total content of the plasticized starch material and the thermoplastic resin in the resin composition of the present invention is, for example, preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 30% by mass or more, and even more preferably 50% by mass or more, based on the total amount of the resin composition.
[0026] The resin composition of the present invention will be described in more detail below.
[0027] [Plasticized starch material]
[0028] By using the plasticized starch material in a resin composition, excellent moldability can be achieved when producing a plastic molded article from the resin composition, and the physical properties of the plastic molded article can be improved. For example, when the content of a previously known starch material (e.g., a non-gelatinized starch material) in a resin composition is 50% by mass or more, molding using the resin composition may not be possible, or even if molding is possible, the molded product may not have good quality. Specifically, when the resin composition is used for inflation molding, the resin composition may not expand, or foaming may occur in the resin composition. Furthermore, even if the resin composition expands, the film obtained by the molding has poor elasticity, so that the film is easily cut and may not have excellent strength. Furthermore, when the resin composition is used to produce a nonwoven fabric by a spunbonding method or a meltblowing method, it may not be possible to obtain the nonwoven fabric due to the occurrence of yarn breakage. Even if a nonwoven fabric is obtained, it may not be possible to obtain a strong nonwoven fabric because the strength of the yarn obtained by the spinning is low.
[0029] Since the resin composition of the present invention contains the plasticized starch material, it has excellent moldability and is suitable for molding, for example, a film or sheet. That is, the resin composition of the present invention can be used to mold a film or sheet. In addition, since the resin composition of the present invention contains the plasticized starch material, it has excellent physical properties (for example, tensile elongation, etc.). Furthermore, since the resin composition of the present invention contains the plasticized starch material, it has excellent spinnability and is suitable for producing, for example, nonwoven fabrics. That is, the resin composition of the present invention can be used to produce nonwoven fabrics. Furthermore, since the resin composition of the present invention contains the plasticized starch material, it has excellent physical properties (for example, tensile strength, etc.).
[0030] The plasticized starch material used in the present invention does not have any foamed portion. The foaming may be caused, for example, by the evaporation of volatile components during the production of the plasticized starch material. The resin composition produced using the plasticized starch material having foamed portions may have poor moldability and spinnability, and may also have a poor appearance.
[0031] The plasticized starch material contained in the resin composition of the present invention may be a material containing starch as a main component. The content of starch in the plasticized starch material may be, for example, preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, based on the total amount of the plasticized starch material. The content of starch in the plasticized starch material may be, for example, preferably 99.5% by mass or less, more preferably 99% by mass or less, and even more preferably 98% by mass or less, based on the total amount of the plasticized starch material. The content of starch may be measured by TG measurement (thermogravimetric analysis) at 150°C. Specifically, the content may be determined based on the amount of mass change measured using a TG measurement device (STA7200, Hitachi High-Tech Science Corporation). The amount of mass change corresponds to the amount of reduction in volatile components, and the amount of reduction corresponds to the amount of polar organic compounds capable of gelatinizing or plasticizing the starch. Therefore, the starch content in the plasticized starch material can be calculated by the following formula: (starch content in the plasticized starch material (unit: mass %))=(mass after starting to measure the amount of mass change) / (mass before starting to measure the amount of mass change)×100. The conditions for measuring the amount of mass change are as follows: temperature range 25° C. to 150° C., heating rate 20° C. / min, under nitrogen.
[0032] In this specification, the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature refers to a polar organic compound capable of gelatinizing or plasticizing starch by contacting with starch at a temperature higher than room temperature. As the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, organic compounds known in the art may be used.
[0033] The polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature refers to a polar organic compound that is not capable of gelatinizing or plasticizing starch at room temperature but is capable of gelatinizing or plasticizing starch at a temperature higher than room temperature. In this specification, the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature is also referred to as a "polar organic compound capable of gelatinizing or plasticizing starch at a high temperature". For example, if a polar organic compound does not gelatinize or plasticize starch even when it is contacted with starch at room temperature for 1 hour, but the starch is gelatinized or plasticized by contacting the polar organic compound with starch at a high temperature for 1 hour, the polar organic compound is "capable of gelatinizing or plasticizing starch at a high temperature". The polar organic compound capable of gelatinizing or plasticizing starch may be any of a polar organic compound capable of gelatinizing starch, a polar organic compound capable of plasticizing starch, and a polar organic compound capable of gelatinizing and plasticizing starch. In this specification, a temperature higher than room temperature (also referred to as "high temperature") refers to a temperature achieved by heat treatment. The high temperature may be, for example, a temperature of 50°C or higher, preferably a temperature of 60°C or higher, more preferably a temperature of 80°C or higher, and even more preferably a temperature of 100°C or higher. In this specification, room temperature refers to the temperature when no heat treatment is performed. Room temperature can be, for example, less than 50°C, preferably 10 to 40°C, more preferably 15 to 35°C, and even more preferably 20 to 30°C.
[0034] Preferably, the total content of polar organic compounds capable of gelatinizing or plasticizing the starch at a temperature higher than room temperature in the plasticized starch material may be, for example, preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 50% by mass or less, based on the total amount of the plasticized starch material. The total content of polar organic compounds capable of gelatinizing or plasticizing the starch at a temperature higher than room temperature in the plasticized starch material may be, for example, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more, based on the total amount of the plasticized starch material. The total content of polar organic compounds capable of gelatinizing or plasticizing the starch at a temperature higher than room temperature is calculated by subtracting the content of gelatinized starch measured by the TG measurement described above from 100% by mass.
[0035] In one embodiment of the present invention, the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature is preferably liquid at room temperature, which allows easy mixing with starch.
[0036] The polar organic compound constituting the plasticized starch material, which is capable of gelatinizing or plasticizing starch at a temperature (high temperature) higher than room temperature, may contain at least one polyhydric alcohol.
[0037] In the present invention, the polyhydric alcohol refers to an alcohol having two or more hydroxyl groups in the molecule. Such a polyhydric alcohol may be a polyhydric alcohol having preferably 2 to 5 carbon atoms, more preferably 2 to 4 carbon atoms. The polyhydric alcohol preferably has 2 to 5 hydroxyl groups (OH groups), more preferably 2 to 4 hydroxyl groups (OH groups). The polyhydric alcohols may include, for example, glycerin and glycols, such as ethylene glycol and propylene glycol. The polyhydric alcohol may preferably include one or a combination of two or more selected from glycerin, ethylene glycol, and propylene glycol. The plasticized starch material of the present invention may preferably include 10 to 40 parts by mass, and more preferably 20 to 35 parts by mass, of the polyhydric alcohol relative to 100 parts by mass of starch. The content of the polyhydric alcohol in the resin composition may preferably be 3% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more.
[0038] In order to suppress the occurrence of bleeding under high temperature and humidity conditions, the content of glycerin in the resin composition is preferably 0% by mass or more and 10% by mass or less, more preferably 0% by mass or more and 9% by mass or less, and even more preferably 0% by mass or more and 7% by mass or less. The smaller the amount of glycerin, the more the occurrence of bleeding can be suppressed. Therefore, it is preferable to use other polyhydric alcohols or the like instead of glycerin without using glycerin, and for example, it is preferable to use ethylene glycol or propylene glycol instead of glycerin. That is, in order to suppress the occurrence of bleeding, it is also possible to contain only ethylene glycol or propylene glycol without containing glycerin at all.
[0039] However, the starch granules may become larger as the glycerin content decreases. In order to make the starch granules smaller even when the glycerin content is decreased, the resin composition of the present invention may further contain an organic acid. The organic acid refers to an organic compound that exhibits acidity, and the organic compound refers to a compound having at least one carbon atom. Examples of the organic acid include carboxylic acid, sulfonic acid, sulfinic acid, organic phosphinic acid, and organic phosphonic acid.
[0040] Examples of the carboxylic acid include monocarboxylic acids such as lactic acid, gluconic acid, acetic acid, and acetic anhydride; dicarboxylic acids such as tartaric acid, maleic acid, maleic anhydride, adipic acid, succinic acid, succinic anhydride, and malic acid; and carboxylic acids having three or more carboxyl groups such as citric acid. Examples of the sulfonic acid include benzenesulfonic acid and methanesulfonic acid. Examples of the sulfinic acid include benzenesulfinic acid and cystinesulfonic acid. Examples of the organic phosphinic acid include diethylphosphinic acid. Examples of the organic phosphonic acid include methylphosphonic acid.
[0041] In one embodiment of the invention, the plasticized starch material comprises a polyhydric alcohol, such as a combination of glycerin and ethylene glycol, or ethylene glycol alone, which may contain an organic acid.
[0042] The plasticized starch material is a starch material that has been gelatinized or plasticized by heating starch in the presence of a polar organic compound capable of gelatinizing or plasticizing the starch at a temperature higher than room temperature. The gelatinization or plasticization may be brought about, for example, by breaking intermolecular bonds (mainly hydrogen bonds) by heating in the presence of a polar organic compound capable of gelatinizing or plasticizing at high temperature. The gelatinized or plasticized starch material may be, for example, pregelatinized starch. It is believed that the plasticization contributes to imparting transparency and / or smoothness to the resin composition of the present invention.
[0043] The plasticization is also believed to contribute to the reduction of starch granules contained in the molded article formed from the resin composition of the present invention. For example, in the case of a molded article formed from a resin composition containing unplasticized starch, the starch particles are likely to appear on the surface of the molded article. The starch particles have a particle size of, for example, about 20 μm. Therefore, for example, when a film is formed using a resin composition containing unplasticized starch, the content of the starch in the resin composition is limited to, for example, a maximum of about 30 mass% relative to the total amount of the resin composition in order to prevent the particle shape of the starch from appearing on the surface of the film. In addition, when the thickness of the film is about 20 μm or less, the starch particles are prominently displayed on the film surface. In addition, when a nonwoven fabric is produced from a resin composition containing unplasticized starch, the fiber forming the nonwoven fabric has a thickness of about 20 to 30 μm, while the particle diameter of the starch is 20 μm, and the size of the starch grains is almost the same as the thickness of the fibers, so that the starch grains protrude outside the fibers and cause thread breakage. On the other hand, since the starch contained in the resin composition of the present invention is plasticized, the particle diameter of the starch grains is 2 μm or less, and the starch grains do not protrude outside the fibers, so that thread breakage does not occur. In addition, since the particle diameter of the starch grains is small, thin threads such as nonwoven fabrics and those with high transparency can be provided. Furthermore, since the particle diameter of the starch is small, the shape of the starch is not easily shown on the surface of the resin composition. Therefore, the content ratio of starch in the resin composition of the present invention can be more than 30 mass% with respect to the total amount of the resin composition, and may be, for example, 50% or more, particularly 60% or more, and more particularly 70% or more. Even if the content of the starch is high, the surface of the resin composition or molded article is smooth.
[0044] The starch used in the present invention may include underground starch and aboveground starch. Underground starch is starch accumulated underground, for example, in rhizomes or roots, etc. Examples of underground starches include, but are not limited to, tapioca starch (cassava starch), potato starch, sweet potato starch, kudzu starch, and bracken starch. Terrestrial starch refers to starch accumulated above ground, for example, starch accumulated in seeds, etc. Terrestrial starches include, but are not limited to, corn starch, wheat starch, sago starch, acorn starch, and rice starch. In the present invention, preferably, underground starch is used. By producing the resin composition of the present invention using underground starch, the odor of the resin composition can be further reduced. The starch used in the present invention may be a modified starch (i.e., modified starch), particularly a modified starch of underground starch. Such modified starches include physically modified starches or chemically modified starches. Examples of physically modified starches include alpha starch and heat-moisture starch. Examples of chemically modified starches include acetoacetate esterified starch, acetate esterified starch, hydroxymethyl etherified starch, hydroxypropyl etherified starch, carboxymethyl etherified starch, allyl etherified starch, methyl etherified starch, succinate esterified starch, xanthogen acetate esterified starch, nitrate esterified starch, urea phosphate esterified starch, phosphate esterified starch, phosphate cross-linked starch, formaldehyde cross-linked starch, acrolein cross-linked starch, epichlorohydrin cross-linked starch, etc. Modified starches can be plasticized at a lower temperature than unmodified starch. Therefore, odor and / or coloring that accompanies heating during the production of plasticized starch can be suppressed.
[0045] The starch used in the present invention may preferably contain equilibrium moisture. The amount of equilibrium moisture may be, for example, preferably 10% to 15% by mass, more preferably 10% to 14% by mass, even more preferably 10% to 13% by mass, and even more preferably 11% to 13% by mass, based on the mass of the starch. It is preferable to use starch or modified starch containing equilibrium moisture within the above numerical range in order to produce the plasticized starch material according to the present invention. When starch not containing equilibrium moisture is used, the starch may not be plasticized.
[0046] According to one embodiment of the present invention, the plasticized starch material may comprise a plasticizer of starch or a plasticizer of modified starch. For example, the starch may be corn starch or tapioca starch. More preferably, the plasticized starch may be a plasticized product of one starch or a combination of two or more starches selected from tapioca starch (cassava starch), potato starch, sweet potato starch, kudzu starch, and bracken starch, or a plasticized product of one modified starch or a combination of two or more modified starches. Even more preferably, the plasticized starch is a plasticized product of tapioca starch or a plasticized product of modified tapioca starch. These plasticized products are particularly preferred from the viewpoints of reducing the odor of the plasticized starch material and reducing the odor of the resin composition of the present invention.
[0047] According to one embodiment of the present invention, the plasticized starch material may contain cellulose nanofibers (hereinafter, also referred to as CNF). It is often difficult to disperse CNF in a thermoplastic resin. The plasticized starch material can easily disperse CNF in the material, and further, the plasticized starch material containing CNF can be easily mixed with a thermoplastic resin. Therefore, the plasticized starch material can easily disperse CNF in a thermoplastic resin. By containing CNF in the resin composition of the present invention, the tensile properties and impact strength of a molded article formed from the resin composition can be improved. In an embodiment in which the plasticized starch material contains CNF, CNF may be added to the thermoplastic resin.
[0048] The benefits of including CNF in the plasticized starch material are described in more detail below. CNF is hydrophilic. CNF is generally produced by disintegrating cellulose materials with water to produce nano-sized particles, and is therefore dispersed in water. CNF is used, for example, to increase the strength of thermoplastic resins. However, since thermoplastic resins are often hydrophobic, it can be difficult to mix hydrophilic CNF with thermoplastic resins. Therefore, for example, CNF modified to be hydrophobic (particularly powdered CNF) is mixed with thermoplastic resins. For the hydrophobization, for example, the TENPO oxidation method can be used. In addition, the CNF dispersion obtained by replacing the water in which CNF is dispersed with the solvent is mixed with a liquid resin (for example, an epoxy resin or a vinyl chloride resin). In addition, the cellulose material is directly crushed with an extruder without being crushed with water, and the CNF obtained as a result of the crushing is mixed with a thermoplastic resin. Such a mixing method can be costly (for example, labor, expense, or time). Therefore, a method in which the CNF dispersed in water is used as it is is desirable. In addition, as mentioned above, it is difficult to disperse CNF in a thermoplastic resin, and if the dispersion is poor, it is possible to improve only one of the tensile elongation and tensile strength of the resulting CNF-containing thermoplastic resin. In addition, CNF is generally in a state of being dispersed in water, for example, the CNF content in a CNF aqueous dispersion is about several mass %, and the CNF aqueous dispersion has a high water content, so it is often difficult to mix the CNF aqueous dispersion with a thermoplastic resin. As described above, the plasticized starch material used in the present invention allows CNF to be easily dispersed in the material, and further allows the plasticized starch material containing CNF to be easily mixed with a thermoplastic resin. The CNF may be a CNF dispersed in water. Even if a water dispersion of CNF is used, by using the water dispersion of CNF in the production of the plasticized starch material, the CNF can be easily dispersed in the thermoplastic resin without using the mixing method described above. Furthermore, when the plasticized starch material containing CNF is mixed with a thermoplastic resin, the CNF is well dispersed in the thermoplastic resin, thereby improving both the tensile elongation and tensile strength of the thermoplastic resin. In addition, when the biomass content or biodegradable resin content in a resin composition is increased, the tensile strength of the resin composition may decrease. By mixing the plasticized starch material containing CNF with a thermoplastic resin as described above, the problem of decreased tensile strength caused by a high biomass content or biodegradable resin content in a resin composition can be solved. Furthermore, other effects brought about by CNF can also be expressed in the resin composition. The CNF contained in the plasticized starch material may be, for example, CNF dispersed in water produced by the general production method described above. In addition to the CNF dispersed in water, modified CNF such as the hydrophobized CNF described above may be contained in the plasticized starch material. Powdered CNF can also be dispersed in the plasticized starch material by dispersing it in water. In this way, the plasticized starch material can disperse various CNFs in the material. Note that CNF dispersed in water is preferred as the CNF dispersed in the plasticized starch material from the viewpoints of cost and ease of handling. CNF dispersed in water is particularly easy to introduce into the production equipment of the plasticized starch material. CNF dispersed in a hydrophilic liquid other than water may also be used. The CNF dispersed in the plasticized starch material may be dispersed in one hydrophilic liquid or in a mixture of two or more hydrophilic liquids. That is, the liquid in which the CNF dispersed in the plasticized starch material is dispersed may be one or a combination of two or more selected from water, glycerin, ethylene glycol, propylene glycol, formamide, and urea water. The liquid may be one or a combination of two or more of the polyhydric alcohols mentioned above.
[0049] Commercially available CNF may be used in the present invention. In the present invention, CNF may mean fibrous cellulose having an average fiber diameter of 10 nm to 3000 nm, which is poorly soluble in a solvent, unlike molecular cellulose. The average fiber diameter is preferably 10 nm to 1000 nm, more preferably 10 nm to 500 nm, even more preferably 10 nm to 300 nm, and even more preferably 10 nm to 100 nm. The aspect ratio of CNF may be, for example, preferably 30 to 10000, more preferably 50 to 5000, and even more preferably 50 to 1000. The aspect ratio is a value obtained by dividing the average fiber length by the average fiber diameter. The average fiber length and average fiber diameter are the average values of 10 arbitrary cellulose fibers observed under an electron microscope.
[0050] The plasticized starch material may be produced by the production method described below.
[0051] [Thermoplastic resin]
[0052] The thermoplastic resin contained in the resin composition of the present invention may be preferably a polyolefin resin or a polyester resin, or a mixture of these resins. The thermoplastic resin may be a polystyrene resin.
[0053] A polyolefin resin is a polymer obtained by polymerization of olefins (e.g., α-olefins) as the main monomers. The polyolefin resin may be, for example, a polyethylene (PE) resin, a polypropylene (PP) resin, or a combination thereof. The polyethylene resin may be, for example, a low density polyethylene resin (LDPE: Low Density Polyethylene), a high density polyethylene resin (HDPE: High Density Polyethylene), a very low density polyethylene resin (VLDPE: Very Low Density Polyethylene), a linear low density polyethylene resin (LLDPE: Linear Low Density Polyethylene), or an ultra high molecular weight polyethylene resin (UHMW-PE: Ultra High Molecular Weight-Polyethylene), or a combination thereof. The polypropylene resin may be, for example, a homopolymer polypropylene resin, or a random or block copolymer polypropylene resin (eg, an ethylene-propylene copolymer, etc.), or a combination thereof. The polyolefin resin may be preferably a biomass-derived polyolefin resin (e.g., a biomass-derived polyethylene resin), and may be, for example, a biomass polyethylene resin. The biomass polyethylene resin may be, for example, LDPE, LLDPE, or HDPE. This can reduce CO2 emissions. The polyolefin resin may be a polyolefin resin produced using a metallocene catalyst, i.e., the thermoplastic resin may be, for example, a metallocene-catalyzed polyethylene resin or polypropylene resin, or a combination thereof. The polystyrene resin may also be a metallocene catalyst-based polystyrene resin.
[0054] The polyester resin is a polymer in which monomers are polymerized through ester bonds. The polyester resin may be, for example, polyethylene terephthalate resin (PET), polyethylene naphthalate resin (PEN), polybutylene terephthalate resin (PBT), polylactic acid resin (PLA), polycarbonate resin (PC), polybutylene adipate terephthalate resin (PBAT), polybutylene succinate resin (PBS), polyhydroxyalkanoate resin (PHA), or a combination of two or more of these.
[0055] Polystyrene resins are polymers formed by polymerization of styrene monomers. Examples of the polystyrene resins include polystyrene resins, rubber-reinforced polystyrene resins (high impact polystyrene resins, HIPS), acrylonitrile-styrene copolymers (AS resins), methacrylate ester-styrene copolymers, acrylonitrile-acrylic rubber-styrene copolymers, and acrylonitrile-ethylene propylene-styrene copolymers, or combinations of two or more of these.
[0056] The type of thermoplastic resin constituting the resin composition of the present invention may be appropriately selected by a person skilled in the art depending on, for example, the type of molded article formed from the resin composition, but a thermoplastic resin with a low processing temperature is preferred. For example, when forming a film or sheet from the resin composition, the thermoplastic resin may be, for example, preferably a polyolefin resin, more preferably a polyethylene resin or a polypropylene resin, and even more preferably LLDPE or LDPE. Even if the resin composition of the present invention is heated to the melting point of these resins, odor or coloring caused by heating the plasticized starch material is unlikely to occur. Therefore, it is possible to suppress the occurrence of odor or coloring when the resin composition is heated to produce a molded article.
[0057] The thermoplastic resin contained in the resin composition of the present invention may preferably have a melting point of 90° C. to 180° C., and more preferably have a melting point of 95° C. to 170° C. By using a thermoplastic resin having a lower melting point, the molding temperature can be lowered, and odor or coloring caused by heating the plasticized starch material can be further suppressed.
[0058] The thermoplastic resin may be in the form of pellets or powder, and is mixed, kneaded, and uniformly dispersed during molding using an extruder, injection molding, or the like.
[0059] The resin composition of the present invention may contain the plasticized starch material and the thermoplastic resin in a ratio of, for example, preferably 20 parts by mass:80 parts by mass to 80 parts by mass:20 parts by mass, more preferably 30 parts by mass:70 parts by mass to 80 parts by mass:20 parts by mass, even more preferably 40 parts by mass:60 parts by mass to 80 parts by mass:20 parts by mass, and even more preferably 50 parts by mass:50 parts by mass to 80 parts by mass:20 parts by mass. By using the plasticized starch material, even if the biomass content of the resin composition of the present invention is increased to the above-mentioned numerical range, a molded product having good quality can be produced from the resin composition.
[0060] According to one embodiment of the present invention, the thermoplastic resin may be a biodegradable resin. In this embodiment, both the plasticized starch material and the thermoplastic resin are biodegradable. Therefore, the resin composition according to this embodiment is more environmentally friendly.
[0061] [Other ingredients]
[0062] The resin composition of the present invention may contain other components in addition to the plasticized starch material and the thermoplastic resin, such as a compatibilizer, an oxidative decomposition accelerator, a colorant, and an antioxidant.
[0063] The compatibilizer may be used to improve the compatibility between the plasticized starch material and the thermoplastic resin. Examples of the compatibilizer include carboxylic acid anhydride-modified polyolefins, olefin-based graft-modified products, and olefin-based comonomers. The carboxylic acid anhydride constituting the carboxylic acid anhydride-modified polyolefin may preferably be maleic anhydride. The compatibilizer may be, for example, one or a combination of two or more selected from the group consisting of maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, and maleic anhydride-modified ethylene-propylene copolymer. The olefin-based graft-modified product may be an acid-modified polyolefin, more specifically, a polyolefin graft-modified with an unsaturated carboxylic acid or a derivative thereof. The (unmodified) polyolefin used for graft modification may be, for example, polyethylene, polypropylene, or an ethylene-α-olefin copolymer (ethylene-propylene copolymer), particularly polypropylene. For example, the acid-modified polyolefin described in JP 2010-095671 A may be used.
[0064] Examples of the colorant include titanium oxide and / or carbon black, and examples of the antioxidant include, but are not limited to, a phenol-based antioxidant.
[0065] The resin composition of the present invention may contain a functional agent in addition to the compatibilizer, the oxidative decomposition accelerator, the colorant, and the antioxidant. In this specification, the functional agent means any material that imparts a function to the resin composition and a molded product molded from the resin composition. Examples of such functional agents include antibacterial agents, disinfectants, bacteriostatic agents, germicides, fungicides, deodorants, and deodorants. The functional agent may be at least one selected from a single substance or a complex of antibacterial agents, disinfectants, bacteriostatic agents, germicides, fungicides, deodorants, and deodorants. In the present invention, antibacterial agents, deodorants, and deodorants are preferably used, and deodorants and deodorants are more preferably used. Deodorants and deodorants are both defined as agents that eliminate unpleasant odors such as bad odors. For example, deodorants include those that adsorb unpleasant odors and those that mask unpleasant odors with a pleasant scent. In addition, deodorants include those that suppress the growth of bacteria that cause unpleasant odors. From the viewpoint of compatibility when blended into the resin composition, these functional agents are preferably liquid or water-soluble. In the present invention, it is more preferable to use a deodorant or deodorant that is particularly effective against fecal odor. The resin composition blended with such a deodorant or deodorant is suitable for use as a garbage bag for diaper disposal. The functional agent may be a commercially available one, and is not particularly limited as long as it achieves the effects of the present invention.
[0066] [Resin composition]
[0067] The resin composition of the present invention may be thermoplastic. Specific examples of the composition of the thermoplastic resin composition according to the present invention will be described below.
[0068] According to one embodiment of the present invention, the thermoplastic resin composition may include the plasticized starch material, the thermoplastic resin, and the compatibilizer. The composition ratio of the plasticized starch material and the thermoplastic resin may be, for example, preferably 20 parts by mass: 80 parts by mass to 80 parts by mass: 20 parts by mass, more preferably 30 parts by mass: 70 parts by mass to 80 parts by mass: 20 parts by mass, and even more preferably 50 parts by mass: 50 parts by mass to 80 parts by mass: 20 parts by mass. The content of the compatibilizer may be, for example, preferably 1 part by mass to 10 parts by mass, and more preferably 2 parts by mass to 9 parts by mass, relative to the total amount of the plasticized starch material and the thermoplastic resin (100 parts by mass). In this embodiment, the thermoplastic resin may be, for example, a polyolefin resin, preferably a polyethylene (PE) resin, and more preferably an LLPDE. In this embodiment, the compatibilizer may be, for example, a carboxylic acid anhydride-modified polyolefin, and preferably a maleic anhydride-modified polyethylene. The thermoplastic resin composition according to this embodiment can be used to produce a film or sheet by a molding method such as inflation molding, T-die molding, or calendar molding. In the present invention, the term "film" refers to a thin membrane-like material, and the thickness of the film can be, for example, less than 200 μm, particularly 10 μm or more and less than 200 μm. In the present invention, the term "sheet" refers to a thin plate-like material, and the thickness of the sheet can be, for example, 200 μm or more, particularly 200 μm or more and 1 mm or less. In this embodiment, the thermoplastic resin may be, for example, a biomass-derived thermoplastic resin, in particular a biomass-derived polyethylene resin.
[0069] According to another embodiment of the present invention, the thermoplastic resin composition may include the plasticized starch material, the thermoplastic resin, the compatibilizer, and the oxidative decomposition accelerator. The composition ratio of the plasticized starch material and the thermoplastic resin may be, for example, preferably 20 parts by mass: 80 parts by mass to 80 parts by mass: 20 parts by mass, more preferably 30 parts by mass: 70 parts by mass to 80 parts by mass: 20 parts by mass, and even more preferably 50 parts by mass: 50 parts by mass to 80 parts by mass: 20 parts by mass. The content of the compatibilizer may be, for example, preferably 1 part by mass to 10 parts by mass, and more preferably 2 parts by mass to 9 parts by mass, relative to the total amount of the plasticized starch material and the thermoplastic resin (100 parts by mass). The content of the oxidative decomposition promoter may be, for example, preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, and even more preferably 0.1 to 0.5 parts by mass, relative to 100 parts by mass of the total amount of the plasticized starch material and the thermoplastic resin. In this embodiment, the thermoplastic resin may be, for example, a polyolefin resin, preferably a polyethylene resin, and more preferably an LLPDE. In this embodiment, the compatibilizer may be, for example, a carboxylic acid anhydride-modified polyolefin, and preferably a maleic anhydride-modified polyethylene. The oxidative decomposition accelerator may be a combination of a carboxylate and a rare earth compound. The thermoplastic resin composition according to this embodiment can be used to produce a film or sheet by a molding method such as inflation molding or T-die extrusion. The thickness of the film can be, for example, less than 200 μm, particularly 10 μm or more and less than 200 μm. The thickness of the sheet can be, for example, 200 μm or more, particularly 200 μm or more and 1.5 mm or less. In this embodiment, the thermoplastic resin may be, for example, a biomass-derived thermoplastic resin, in particular a biomass-derived polyethylene resin. The thermoplastic resin composition according to this embodiment has a high biomass content, and the thermoplastic resin contained in the composition is biodegradable.
[0070] According to another embodiment of the present invention, the thermoplastic resin composition may include the plasticized starch material, the thermoplastic resin, and the functional agent. The composition ratio of the plasticized starch material and the thermoplastic resin may be, for example, preferably 20 parts by mass: 80 parts by mass to 80 parts by mass: 20 parts by mass, more preferably 30 parts by mass: 70 parts by mass to 80 parts by mass: 20 parts by mass, and even more preferably 50 parts by mass: 50 parts by mass to 80 parts by mass: 20 parts by mass. The content of the functional agent may be, for example, preferably 1 part by mass to 10 parts by mass, and more preferably 2 parts by mass to 9 parts by mass, relative to a total amount of 100 parts by mass of the plasticized starch material and the thermoplastic resin. In this embodiment, the thermoplastic resin composition may further include the compatibilizer. The content of the compatibilizer may be, for example, preferably 1 part by mass to 10 parts by mass, and more preferably 2 parts by mass to 9 parts by mass, relative to a total amount of 100 parts by mass of the plasticized starch material and the thermoplastic resin. In this embodiment, the composition may further contain the oxidative decomposition promoter. The content of the oxidative decomposition promoter may be, for example, preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, and even more preferably 0.1 to 0.5 parts by mass, relative to 100 parts by mass of the total amount of the plasticized starch material and the thermoplastic resin. In this embodiment, the thermoplastic resin may be, for example, a polyolefin resin, preferably a polyethylene resin, and more preferably an LLPDE. In this embodiment, the compatibilizer may be, for example, a carboxylic acid anhydride-modified polyolefin, and preferably a maleic anhydride-modified polyethylene. The oxidative decomposition accelerator may be a combination of a carboxylate and a rare earth compound. The thermoplastic resin composition according to this embodiment can be used to produce a film or sheet by a molding method such as inflation molding or T-die extrusion. The thickness of the film can be, for example, less than 200 μm, particularly 10 μm or more and less than 200 μm. The thickness of the sheet can be, for example, 200 μm or more, particularly 200 μm or more and 1.5 mm or less. In this embodiment, the thermoplastic resin may be, for example, a biomass-derived thermoplastic resin, in particular a biomass-derived polyethylene resin. The thermoplastic resin composition according to this embodiment has a high biomass content, and the thermoplastic resin contained in the composition is biodegradable.
[0071] The resin composition of the present invention may be used to produce other molded products than films and sheets. Examples of the other molded products include, but are not limited to, containers (e.g., bottle containers), bottle caps, plastic cardboard, nonwoven fabrics, and monofilaments. For example, the resin composition of the present invention may be used for blow molding, injection molding, profile extrusion molding, and spinning (e.g., melt spinning). For example, a bottle container can be molded by the blow molding. For example, a bottle cap or a container can be manufactured by the injection molding. For example, a plastic cardboard can be molded by the profile extrusion molding. For example, a monofilament can be molded by the spinning (e.g., melt spinning).
[0072] The resin composition of the present invention may be produced by the production method described below.
[0073] [Film or sheet]
[0074] The present invention also provides a resin composition formed into the shape of a film or sheet. The film or sheet may be a single-layer film or sheet composed only of a layer formed from the resin composition according to the present invention, or may be a multi-layer film or sheet in which at least one layer formed from the resin composition according to the present invention and at least one layer formed from another composition (particularly a resin composition) are laminated. The film may have a thickness of, for example, less than 200 μm, particularly a thickness of 10 μm or more and less than 200 μm. The sheet may have a thickness of, for example, 200 μm or more, particularly a thickness of 200 μm or more and 1.5 mm or less.
[0075] According to one embodiment of the present invention, the film or sheet has a surface having an average roughness (Ra) measured according to JIS B0031 of preferably 2 μm or less, more preferably 1.8 μm or less, and even more preferably 1.5 μm or less, and the surface is a surface of a layer formed from a resin composition according to the present invention. The average roughness may be measured by a surface roughness meter according to JIS B0031. The resin composition of the present invention can provide a film or sheet having such a smooth surface. The film or sheet provided by the resin composition of the present invention can be suitably used for cards, packaging, containers, separators, covers, partitions, laminates, and bags.
[0076] The sheet or film of the present invention can be produced by using a conventional molding technique for petroleum-based plastics. For example, the plasticized starch material and the thermoplastic resin may be mixed in a mixer such as a Henschel mixer, a tumbler mixer, a Barbary mixer, or a kneader mixer, and then a sheet may be formed using a T-die extruder or a calendar molding machine, or a film may be formed using an inflation molding machine. Alternatively, the raw materials such as the plasticized starch material and the thermoplastic resin may be directly kneaded, mixed, and molded, or the raw materials may be mixed in a mixer, and then strands may be extruded using a single-screw or twin-screw extruder, cut, and pelletized, and the pellets may be used as a master batch to mold a sheet or film.
[0077] The molding temperature range employed in producing a sheet or film is preferably in the range of 95 to 200°C when the raw materials are directly kneaded, mixed, and molded, from the viewpoint of suppressing the occurrence of scorching or decomposition of the raw materials and burning inside the cylinder, and from the viewpoint of suppressing the plasticized starch material being discharged in an unmolten state, which may cause problems along with an increase in pressure. Also, when master pellets are produced and molded, the range of 95 to 200°C is preferably used.
[0078] In order to prevent the raw material from burning or decomposing, the residence time in the cylinder is preferably within 10 minutes at most.
[0079] The sheet extrusion molded by the T-die extruder may be cooled, taken up, and wound up by setting the temperature of the take-up roll to 60° C. or less and forming the sheet to a predetermined thickness. The film extrusion molded by the inflation molding machine may be cooled, taken up, and wound up by setting the temperature of the take-up roll to 90° C. or less and forming the film to a predetermined thickness.
[0080] [Laminate]
[0081] The present invention also provides a laminate in which the surface of the film or sheet is covered with a membrane. The laminate may be one in which one surface of the film or sheet is covered with a membrane, or both surfaces of the film or sheet are covered with a membrane. By covering the surface of the film or sheet with a membrane, bleeding out from the surface on the covered side can be suppressed. The membrane may be, for example, a polyolefin-based resin such as polyethylene (PE) resin, polypropylene (PP) resin, or a combination of two or more of these, or may be, for example, a polylactic acid resin (PLA), or a polycarbonate resin (PC), polyethylene terephthalate resin (PET), polyethylene naphthalate resin (PEN), polybutylene terephthalate resin (PBT), polybutylene adipate terephthalate resin (PBAT), polybutylene succinate resin (PBS), polyhydroxyalkanoate resin (PHA), or a combination of two or more of these polyester-based resins. An adhesive layer may be provided between the film or sheet and the membrane. For such an adhesive layer, a resin having a melting point lower than the melting point of the resin composition forming the film or sheet may be used. Examples of the resin used for such an adhesive layer include epoxy resins and urethane resins.
[0082] In the laminate, the film may have a thickness of, for example, less than 200 μm, particularly 10 μm or more and less than 200 μm. The sheet may have a thickness of, for example, 200 μm or more, particularly 200 μm or more and 1.5 mm or less. The membrane may have a thickness of, for example, less than 60 μm, particularly 10 μm or more and less than 50 μm. The laminate provided by the resin composition of the present invention may be suitably used for cards, covers, packaging, containers, separators, partitions, bags, and laminates.
[0083] [Nonwoven fabric]
[0084] The present invention also provides a nonwoven fabric formed from the resin composition of the present invention. The fiber diameter of the fibers constituting the nonwoven fabric is preferably 5 to 30 μm, more preferably 5 to 25 μm, and even more preferably 5 to 20 μm. The average single fiber fineness of the fibers constituting the nonwoven fabric is preferably 0.16 dtex or more and 20 dtex or less, more preferably 0.17 dtex or more and 15 dtex or less, and even more preferably 0.17 dtex or more and 10 dtex or less. From the viewpoint of spinning stability, the average single fiber fineness is preferably 0.17 dtex or more. On the other hand, the finer the fineness, the more adhesion points of the yarns in the nonwoven fabric, so that the strength is high and the flexibility is likely to be good. From the viewpoint of the strength of the nonwoven fabric, the average single fiber fineness is preferably 0.2 dtex or less. The average single fiber fineness is determined by the fiber cross-sectional area A (m 2 ) and polymer density ρ(g / m 3 ) can be calculated using the following formula: Single fiber size (dtex) = A(m 2 )×ρ(g / m 3 )×10000(m).
[0085] In the present invention, the nonwoven fabric preferably has a basis weight of 10 to 200 g / m 2 and more preferably 10 to 190 g / m 2 and more preferably 20 to 180 g / m 2By setting the basis weight within the above range, sufficient strength can be obtained, particularly when used as a nonwoven fabric for shopping bags.
[0086] In the present invention, the apparent density of the nonwoven fabric is preferably 0.3 g / cm 3 More preferably, it is 0.2 g / cm 3 More preferably, it is 0.15 g / cm or less. 3 By setting the apparent density within the above range, sufficient bulkiness can be obtained, particularly when used as a nonwoven fabric for wiping. The apparent density can be calculated by dividing the basis weight by the thickness.
[0087] The nonwoven fabric of the present invention may be produced by a spunbonding method, a meltblowing method, etc. For example, the spunbonding method is a production method in which the resin composition of the present invention is heated and melted, spun from a spinneret, and the cooled and solidified filaments are pulled and stretched by an ejector, collected and deposited on a moving net to form a web, and then heat-pressurized and thermally bonded by an embossing roller.
[0088] The shape of the spinneret and ejector may be various, such as round or rectangular. Among them, a combination of a rectangular spinneret and a rectangular ejector is preferably used, since the amount of compressed air used is relatively small and filaments are less likely to melt or rub against each other. The spinneret preferably has a round discharge shape.
[0089] The spinning temperature during melting and spinning is preferably 200 to 300° C., more preferably 210 to 280° C., and even more preferably 220 to 260° C. By setting the spinning temperature within the above range, a stable molten state can be achieved, and excellent spinning stability can be obtained. The resin composition (raw material) is melted and measured by an extruder, supplied to a spinneret, and spun out from the nozzle of the spinneret.
[0090] The spun filament fibers can be cooled by any of the usual methods, for example, by blowing cooling air onto the filaments spun from the spinneret.
[0091] The cooled and solidified fibers are pulled and stretched by compressed air ejected from an ejector. The filaments are then collected on a moving net to form a nonwoven web, and the resulting nonwoven web is integrated by thermal bonding to obtain a nonwoven fabric.
[0092] Examples of the thermal bonding method include a thermal embossing roll, a pair of upper and lower rolls each having an engraving (uneven portion) on their surface, a thermal embossing roll consisting of a combination of a roll with one roll having a flat (smooth) surface and a roll with an engraving (uneven portion) on the other roll surface, and a thermal calendar roll consisting of a pair of upper and lower flat (smooth) rolls. Alternatively, ultrasonic fusion may be used.
[0093] Among them, from the viewpoints of strength and abrasion resistance, thermal bonding using an embossed roll is preferably adopted. Also, from the viewpoint of preventing pressure from being applied to the entire surface, it is preferable to use a roll with engraving (uneven portions) on either the top or bottom.
[0094] The shapes of the engravings on the hot embossing rolls can be circular, oval, square, rectangular, flat, etc. Shapes such as rectangular rectangles, rhombuses, regular hexagons and regular octagons can be used.
[0095] The surface temperature of the hot embossing roll may be preferably −50 to −5° C. relative to the melting point of the resin composition. By setting the surface temperature of the hot embossing roll to be preferably −50° C. or higher, more preferably −40° C. or higher, and even more preferably −30° C. or higher, relative to the melting point of the resin composition, sufficient thermal adhesion can be achieved, strength can be imparted, and generation of fluff can be easily suppressed.
[0096] Furthermore, by setting the surface temperature of the hot embossing roll to be −5° C. or lower than the melting point of the resin composition, peeling of the resin layers due to melting of the fibers can be easily prevented.
[0097] The line pressure of the hot embossing roll during thermal bonding can be preferably 5 to 50 kgf / cm. By setting the line pressure to preferably 5 kgf / cm or more, more preferably 10 kgf / cm or more, and even more preferably 15 kgf / cm or more, sufficient thermal bonding can be achieved. On the other hand, by setting the line pressure to preferably 50 kgf / cm or less, more preferably 40 kgf / cm or less, and even more preferably 30 kgf / cm or less, the roll stress is not applied too much, and bulkiness can be maintained. The nonwoven fabric provided by the resin composition of the present invention can be suitably used for covers, bags, various filters, wet sheets, masks, separators, containers, and packaging.
[0098] 2.Plasticized starch
[0099] The plasticized starch of the present invention has a plasticized starch material containing starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and water. The plasticized starch of the present invention preferably has a durometer type D hardness of 20 or more, more preferably 23 or more, and even more preferably 25 or more. All of the explanations regarding the plasticized starch material in "1. Resin composition" above (e.g., details of the composition and each component, etc.) also apply to the plasticized starch material used in the plasticized starch of the present invention, so the explanation of the plasticized starch material of the present invention will be omitted. The plasticized starch material has the effects as described in "1. Resin composition" above. For example, the plasticized starch material can reduce the particle size of starch contained in the resin composition, and can also suppress bleeding out of various additives from the surface under high temperature and humidity conditions.
[0100] The plasticized starch of the present invention preferably does not have a foamed portion. Foaming may occur due to evaporation of volatile components in the production of the plasticized starch material. The plasticized starch of the present invention may be used to produce a plasticized starch-containing resin composition containing starch granules having a particle diameter of 2 μm or less. The plasticized starch of the present invention may contain the functional agent in addition to the compatibilizer, the oxidative decomposition promoter, the colorant, and the antioxidant. Examples of such functional agents include antibacterial agents, disinfectants, bacteriostatic agents, bactericides, fungicides, deodorants, and deodorants. The functional agent may be at least one selected from the simple substances or complexes of antibacterial agents, disinfectants, bacteriostatic agents, bactericides, fungicides, deodorants, and deodorants. In the present invention, antibacterial agents, deodorants, and deodorants are preferably used, and deodorants and deodorants are more preferably used.
[0101] 3. Manufacturing method of resin composition
[0102] [One embodiment of the method for producing a resin composition]
[0103] One embodiment of a method for producing a resin composition according to the present invention includes a first mixing step of mixing starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and water, a plasticized starch preparation step of heating the mixture obtained in the first mixing step to plasticize the starch and prepare a plasticized starch, and a second mixing step of mixing the plasticized starch and a thermoplastic resin to obtain a resin composition containing starch granules having a particle size of 2 μm or less. According to one embodiment of the method for producing a resin composition of the present invention, the resin composition of the present invention described above in "1. Resin composition" can be produced.
[0104] Each step of the manufacturing method will be described below.
[0105] (1) First mixing step
[0106] In the first mixing step, starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and water are mixed together. The starch and the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature are as described above in "1. Resin composition," and the same description also applies to the present production method.
[0107] In the first mixing step, the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature may be mixed with the starch in an amount of preferably 5 to 40 parts by mass, more preferably 10 to 40 parts by mass, and even more preferably 20 to 40 parts by mass, per 100 parts by mass of the starch. The polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature may contain at least one polyhydric alcohol. Examples of such polyhydric alcohol include one or a combination of two or more selected from ethylene glycol, propylene glycol, and glycerin, and preferably ethylene glycol and propylene glycol.
[0108] The polyhydric alcohol may more preferably contain glycerin and / or ethylene glycol. In the first mixing step, glycerin and ethylene glycol may be used at a ratio of glycerin mass to ethylene glycol mass of, for example, preferably 1:8 to 0.5:1, more preferably 1:4 to 1:1, and even more preferably 1:3 to 1:1. The polyhydric alcohol may more preferably contain glycerin and / or propylene glycol. In the first mixing step, glycerin and propylene glycol may be used at a ratio of glycerin mass to propylene glycol mass of, for example, preferably 1:8 to 0.5:1, more preferably 1:4 to 1:1, and even more preferably 1:3 to 1:1. The polyhydric alcohol may be only glycerin. Furthermore, the polyhydric alcohol may not contain glycerin, and may be only ethylene glycol or only propylene glycol. In addition, from the viewpoint of suppressing the occurrence of bleeding, when only glycerin is used, glycerin is mixed with the starch in an amount of preferably 40 parts by mass or less, more preferably 38 parts by mass or less, and even more preferably 35 parts by mass or less, per 100 parts by mass of the starch.
[0109] When the amount of glycerin as the polyhydric alcohol is 25 parts by weight or less, from the viewpoint of reducing the size of starch particles in the resin composition, an organic acid may be preferably included. Such an organic acid may be, for example, succinic acid, malic acid, maleic acid, tartaric acid, adipic acid, gluconic acid, lactic acid, etc., or an anhydride thereof. As the organic acid, from the viewpoint of preventing discoloration and the viewpoint of the balance between price and effect, succinic acid, malic acid, tartaric acid, maleic acid, etc. are preferred, and succinic acid and tartaric acid are more preferred. The organic acid is mixed with the starch in an amount of preferably 0.1 to 5 parts by weight, more preferably 0.3 to 4 parts by weight, and even more preferably 0.5 to 3 parts by weight, relative to 100 parts by weight of the starch.
[0110] The water used in the first mixing step is mixed with the starch in an amount of preferably 10 to 40 parts by mass, more preferably 15 to 30 parts by mass, and even more preferably 20 to 30 parts by mass, per 100 parts by mass of the starch.
[0111] In the first mixing step, the functional agent may be further blended in. The functional agent is mixed with the starch in an amount of preferably 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 2 to 9 parts by mass, per 100 parts by mass of starch.
[0112] The starch used in the first mixing step may be underground starch or aboveground starch, for example, corn starch or tapioca starch. In the present invention, underground starch is preferably used. By producing the resin composition of the present invention using underground starch, the odor of the resin composition can be further reduced. The starch used in the first mixing step may be a modified starch (i.e., modified starch).
[0113] The starch used in the first mixing step may preferably contain equilibrium moisture. The amount of equilibrium moisture may be, for example, preferably 10% to 15% by mass, more preferably 10% to 14% by mass, even more preferably 10% to 13% by mass, and even more preferably 11% to 13% by mass, based on the mass of the starch. It is preferable to use starch or modified starch containing equilibrium moisture within the above numerical range in order to produce the plasticized starch material according to the present invention. When starch not containing equilibrium moisture is used, the starch may not be plasticized.
[0114] The first mixing step may be carried out, for example, using a stirrer. A commercially available device may be used as the stirrer. The first pre-mixing step is preferably carried out at room temperature. By carrying out the first mixing step at room temperature and then carrying out the following plasticized starch preparation step, it is possible to suppress the generation of coloring and / or odor caused by heating starch.
[0115] The starch may, for example, preferably account for 40% by mass to 85% by mass, more preferably 45% by mass to 80% by mass, and even more preferably 50% by mass to 75% by mass of the total amount of raw materials used to produce the plasticized starch.
[0116] (2) Plasticized starch preparation process
[0117] The plasticized starch preparation step includes heating the mixture obtained in the first mixing step in an extruder. The starch is plasticized by the heating to obtain a plasticized starch. The heating may be performed at a temperature of preferably 100°C to 150°C, more preferably 100°C to 140°C, and even more preferably 100°C to 130°C. The extruder may be, for example, a twin-screw extruder or a single-screw extruder, and a commercially available one may be used. The plasticized starch extruded from the extruder may have, for example, a cylindrical (strand) or pellet shape.
[0118] The explanation regarding the plasticized starch material described in "1. Resin composition" above also applies to the plasticized starch in the present production method. For example, the masterbatch has a durometer type D hardness of 20 or more.
[0119] (3) Second mixing step
[0120] In the second mixing step, the plasticized starch prepared in the plasticized starch preparation step is mixed with a thermoplastic resin. The mixing produces a resin composition according to the present invention. The mixing may be performed, for example, using an extruder, preferably a twin-screw extruder. In the mixing step, a compatibilizer may be mixed in addition to the plasticized starch and the thermoplastic resin. The compatibilizer is as described above in "1. Resin composition", and therefore the description thereof will be omitted.
[0121] In the second mixing step, the components to be mixed (e.g., the plasticized starch and the thermoplastic resin, and optionally the compatibilizer) are heated. The heating is performed so as to melt the thermoplastic resin, and may be performed at a temperature of preferably 100°C to 200°C, more preferably 100°C to 190°C, and even more preferably 100°C to 180°C. The components to be mixed may be heated, for example, to a temperature at which the thermoplastic resin melts. The temperature may be appropriately selected by a person skilled in the art depending on the type of thermoplastic resin.
[0122] The manufacturing method may further include a molding step of molding the resin composition obtained in the mixing step. A molded product having a desired shape is manufactured by the molding step. The molding may be, for example, inflation molding or T-die molding. A resin composition molded into a film or sheet shape may be manufactured by such a molding method. The molding temperature may be appropriately selected by a person skilled in the art depending on the type of thermoplastic resin. For example, when the thermoplastic resin is polyethylene, the temperature may be 160°C to 200°C. For example, when the thermoplastic resin is polypropylene, the temperature may be 160°C to 200°C.
[0123] The production method may further include a stretching step of stretching the resin composition molded into a film or sheet shape in the molding step.
[0124] [Another embodiment of the method for producing a resin composition]
[0125] Another embodiment of the method for producing a resin composition according to the present invention includes a mixing step of mixing starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, water, and a thermoplastic resin, and a heating step of plasticizing the starch by heating the mixture obtained in the mixing step, and the particle size of starch granules contained in the obtained resin composition is 2 μm or less. According to another embodiment of the production method of the present invention, the resin composition of the present invention described above in "1. Resin composition" can be produced.
[0126] In another embodiment, unlike the above-described manufacturing method, the raw material components (plasticized starch material, thermoplastic resin, etc.) are directly mixed together without first preparing a plasticized starch.
[0127] Each step of the manufacturing method will be described below.
[0128] (1)Mixing process
[0129] In the mixing step, starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, water, and a thermoplastic resin are mixed together. The starch, the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and the thermoplastic resin are as described above in "1. Resin composition," and the same description also applies to the present production method.
[0130] In the mixing step, the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature is mixed with the starch in an amount of preferably 5 to 40 parts by mass, more preferably 10 to 40 parts by mass, and even more preferably 20 to 40 parts by mass, per 100 parts by mass of the starch.
[0131] The water used in the mixing step is mixed with the starch in an amount of preferably 10 to 40 parts by mass, more preferably 15 to 30 parts by mass, and even more preferably 20 to 30 parts by mass, per 100 parts by mass of the starch.
[0132] In the mixing step, the functional agent may further be mixed in. The functional agent is mixed with the starch in an amount of preferably 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 2 to 9 parts by mass, per 100 parts by mass of the starch.
[0133] The thermoplastic resin used in the mixing step is mixed with the starch in an amount of preferably 10 to 900 parts by mass, more preferably 10 to 800 parts by mass, and even more preferably 15 to 800 parts by mass, per 100 parts by mass of the starch.
[0134] (2)Heating process
[0135] In the heating step, the mixture obtained in the mixing step is heated. The heating can be performed so that the thermoplastic resin melts. The components to be mixed may be heated, for example, to a temperature at which the thermoplastic resin melts. The temperature may be appropriately selected by a person skilled in the art depending on the type of thermoplastic resin. For example, when the thermoplastic resin is polyethylene, the temperature may be 100°C to 170°C. For example, when the thermoplastic resin is polypropylene, the temperature may be 150°C to 200°C. The particle size of starch granules contained in the resin composition produced by the mixing step and the heating step is 2 μm or less.
[0136] 4. Manufacturing method of plasticized starch
[0137] One embodiment of a method for producing a plasticized starch according to the present invention includes a mixing step of mixing starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and water, and a plasticization step of plasticizing the starch by heating the mixture obtained in the mixing step.
[0138] (1)Mixing process In the mixing step, starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, and water are mixed together. The starch and the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature are as described above in "1. Resin composition," and the same description also applies to the present production method.
[0139] In the mixing step, the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature is mixed with the starch in an amount of preferably 5 to 40 parts by mass, more preferably 10 to 40 parts by mass, and even more preferably 20 to 40 parts by mass, per 100 parts by mass of the starch.
[0140] The water used in the mixing step is mixed with the starch in an amount of preferably 10 to 40 parts by mass, more preferably 15 to 30 parts by mass, and even more preferably 20 to 30 parts by mass, per 100 parts by mass of the starch.
[0141] In the mixing step, the functional agent may be mixed in. The functional agent is mixed with the starch in an amount of preferably 1 to 15 parts by mass, more preferably 2 to 10 parts by mass, and even more preferably 2 to 9 parts by mass, per 100 parts by mass of the starch.
[0142] (2)Plasticization process
[0143] In the plasticization step, the mixture obtained in the mixing step is heated in an extruder. The heating can be performed so that the starch is plasticized. The components to be mixed may be heated, for example, to a temperature at which the starch is plasticized. The temperature may be appropriately selected by a person skilled in the art depending on the type of starch. For example, the temperature may be preferably 100°C to 150°C, more preferably 100°C to 140°C, and even more preferably 100°C to 130°C. The extruder may be, for example, a twin-screw extruder or a single-screw extruder, and a commercially available one may be used. The plasticized starch extruded from the extruder may have, for example, a cylindrical (strand) or pellet shape.
[0144] 5. Use of the present invention The film or sheet formed by the resin composition of the present invention by inflation molding, T-die molding, calendar molding, or the like is used for vacuum molding applications such as containers, various release films, release sheets, house films, tunnel films, mulch films, vegetation films, civil engineering sheets, and the like. The bag formed by the resin composition of the present invention by inflation molding is used for shopping bags, garbage bags, compost bags, plastic bags, and the like. The blow molded body formed by the resin composition of the present invention by blow molding or the like is used for blow bottles, beverage bottles, bottle containers, and the like. The injection molded body formed by injection molding of the resin composition of the present invention is used for bottle caps, various food containers, and the like. The nonwoven fabric spun by the resin composition of the present invention by the spunbond method, melt blow method, and the like is used for covers, bags, various filters, wet sheets, masks, separators, containers, and packaging. In addition, when the resin composition of the present invention contains a biodegradable resin in order to reduce the environmental load, the molded body formed by the resin composition is used for the above-mentioned applications. The resin composition of the present invention, which contains cellulose nanofibers to improve strength, is used in the above-mentioned applications. The resin composition of the present invention, which contains functional agents such as deodorants, deodorants, and antibacterial agents, is used in the above-mentioned applications, and is particularly preferably used in various sanitary products such as garbage bags and used diaper storage bags. Furthermore, the resin composition of the present invention is used in applications such as laminates with suppressed bleeding. EXAMPLES
[0145] The present invention will be described in more detail below based on examples. Note that the examples described below are representative examples of the present invention, and the scope of the present invention is not limited to these examples. The evaluation methods and evaluation criteria used in the examples are as follows.
[0146] (1) Presence or absence of bubbles in plasticized starch The presence or absence of air bubbles in the plasticized starch was visually confirmed and evaluated according to the following criteria. A: No air bubbles were generated throughout the plasticized starch. B: Air bubbles were generated in some of the plasticized starch. C: Air bubbles were generated throughout the plasticized starch.
[0147] (2) Physical properties of plasticized starch The physical properties of the plasticized starch were evaluated according to the following criteria. A: Durometer type D hardness was 20 or more. C: The hardness was less than 20 using a durometer type D, or air bubbles were generated (swelled) throughout the plasticized starch, and the hardness could not be measured.
[0148] (3) Starch granule size The surfaces of the film samples or nonwoven fabric samples were observed (secondary electron images) using a SEM (scanning electron microscope) JSM-IT100 (JEOL Ltd.) at an accelerating voltage of 5.0 kV. For each sample, four images of a 200 μm × 250 μm area were taken at a magnification of 500. The particle size of the starch particles in each image was measured using a scale within the field of view.
[0149] (4) Presence or absence of bleed A film sample was used, and a cut sample of 10 cm length and 10 cm width was left to stand for 12 hours in a thermo-hygrostat maintained at 40°C x 80% RH. After 12 hours, the presence or absence of bleeding was evaluated by touch. Specifically, five panelists evaluated the presence or absence of bleeding on the surface of the film sample by touch based on the following criteria. A: There was no bleeding and no stickiness. B: Slight bleeding occurred and there was some stickiness. C: Bleeding occurred and the product was sticky.
[0150] (5) Tensile properties The injection molded products were used to measure the tensile properties (maximum stress, elongation at break, elastic modulus) in accordance with JIS K 7161.
[0151] (6) Izod impact strength The Izod impact strength of the injection molded product was measured in accordance with JIS K 7110.
[0152] (7) Production Efficiency The production efficiency was evaluated based on the cooling time. The shorter the cooling time, the higher the production efficiency.
[0153] Test Example 1: Production and molding of resin composition (film or sheet example)
[0154] Example 1
[0155] As shown in Table 1 below, 100 parts by mass of phosphate cross-linked tapioca starch (T-1, Matsutani Chemical Industry Co., Ltd.), 12 parts by mass of glycerin, 22 parts by mass of ethylene glycol, and 27 parts by mass of water were prepared as plasticized starch materials. These four components were mixed in a mixer. The mixing was carried out at room temperature. The glycerin, ethylene glycol, and water were mixed in advance before being put into the mixer.
[0156] The mixture obtained by this mixing was a powder mixture.
[0157] The mixture obtained by the above mixing was fed into a twin-screw extruder (PCM30, Ikegai Corporation), and the mixture was subjected to a kneading treatment.
[0158] The cylinder temperature during the kneading process was 110° C. During the kneading process, suction was performed from a vent. After the kneading process, the mixture was extruded from the die of the extruder, and an elongated, roughly cylindrical plasticized starch (master batch) was obtained.
[0159] The plasticized starch was evaluated for the presence or absence of bubbles and the durometer hardness according to the above criteria.
[0160] The evaluation results are shown in Table 1 below, and the plasticized starch had no bubbles formed throughout. The plasticized starch also had a hardness of 27 in durometer type D.
[0161] 35 parts by mass of the plasticized starch, 70 parts by mass of polypropylene (PM900C, Sunallomer Co., Ltd.), and 3 parts by mass of a compatibilizer (maleic anhydride modified polypropylene, DuPont Co., Ltd.) were fed into a twin-screw extruder (PCM30, Ikegai Co., Ltd.), and these components were subjected to a kneading treatment. The screw temperature in the kneading treatment was 170°C, and the resin pressure was 4.4 MPa. During the kneading treatment, suction was performed from a vent. Through the kneading treatment, a resin composition (hereinafter also referred to as "resin composition of Example 1") was obtained.
[0162] The resin composition of Example 1 was fed to an inflation molding machine (Placo Corporation, die Φ65, extruder diameter 55 mm, temperature 150° C.), and inflation molding was performed. The inflation molding was performed at 150° C. to 160° C. A film having a thickness of 40 μm was obtained by the inflation molding.
[0163] The moldability in inflation molding, the particle size of the starch particles on the film surface, and the presence or absence of bleeding were evaluated according to the above-mentioned methods and standards. The evaluation results are shown in Table 1 below, and an electron microscope photograph of the obtained film is shown in Figure 1(a). As shown in Figure 1(a), the particle size of the starch particles on the film surface was 2 μm. In addition, slight bleeding occurred on the film surface, and it was slightly sticky.
[0164] [Table 1]
[0165] Example 2
[0166] A plasticized starch was obtained in the same manner as in Example 1, except that 100 parts by mass of phosphate cross-linked tapioca starch, 4 parts by mass of glycerin, 30 parts by mass of ethylene glycol, and 27 parts by mass of water were mixed in the mixer as the plasticized starch material, as shown in Table 1. The glycerin, ethylene glycol, and water were mixed in advance before being charged into the mixer.
[0167] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 2") was obtained in the same manner as in Example 1.
[0168] The resin composition of Example 2 was subjected to inflation molding in the same manner as in Example 1 to obtain a film.
[0169] In Example 2, the same evaluations as in Example 1 were performed. The evaluation results are shown in the above Table 1. As shown in Table 1, the same evaluation results as in Example 1 were obtained for the plasticized starch.
[0170] More specifically, the plasticized starch produced in Example 2 was free of bubbles throughout and had a durometer type D hardness of 27. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. In addition, the film surface was free of bleeding and stickiness.
[0171] Example 3
[0172] A plasticized starch was obtained in the same manner as in Example 1, except that 100 parts by mass of phosphate cross-linked tapioca starch, 7 parts by mass of glycerin, 27 parts by mass of ethylene glycol, and 27 parts by mass of water were mixed in the mixer as the plasticized starch material, as shown in Table 1. The glycerin, ethylene glycol, and water were mixed in advance before being charged into the mixer.
[0173] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 3") was obtained in the same manner as in Example 1.
[0174] The resin composition of Example 3 was subjected to inflation molding in the same manner as in Example 1 to obtain a film.
[0175] In Example 3, the same evaluations as in Example 1 were performed. The evaluation results are shown in the above Table 1. As for the plasticized starch, as shown in the above Table 1, the same evaluation results as in Example 1 were obtained.
[0176] More specifically, the plasticized starch produced in Example 3 was free of bubbles throughout and had a durometer type D hardness of 25. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. In addition, the film surface was free of bleeding and stickiness.
[0177] Example 4
[0178] As shown in Table 1 above, 100 parts by mass of phosphate cross-linked tapioca starch, 12 parts by mass of glycerin, 22 parts by mass of ethylene glycol, and 27 parts by mass of water containing a 2% suspension of CNF (product name: hardwood, Daio Paper Co., Ltd.) were prepared in the mixer as plasticized starch materials, and these four components were mixed in the mixer in the same manner as in Example 1 to obtain a mixture.
[0179] The mixture was kneaded in the same manner as in Example 1 to obtain a plasticized starch containing CNF. The plasticized starch was used to obtain a resin composition (hereinafter also referred to as "resin composition of Example 4") in the same manner as in Example 1.
[0180] The resin composition of Example 4 was subjected to inflation molding in the same manner as in Example 1 to obtain a film.
[0181] In Example 4, the same evaluations were performed as in Example 1. As for the plasticized starch, as shown in Table 1 above, the same evaluation results as in Example 1 were obtained.
[0182] More specifically, the plasticized starch produced in Example 4 was free of bubbles throughout and had a durometer type D hardness of 25. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. In addition, slight bleeding occurred on the film surface, and it was slightly sticky.
[0183] Example 5
[0184] A plasticized starch was obtained in the same manner as in Example 1, except that 100 parts by mass of phosphate cross-linked tapioca starch, 7 parts by mass of glycerin, 27 parts by mass of propylene glycol, and 27 parts by mass of water were mixed in the mixer as the plasticized starch material, as shown in Table 1. The glycerin, propylene glycol, and water were mixed in advance before being charged into the mixer.
[0185] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 5") was obtained in the same manner as in Example 1.
[0186] The resin composition of Example 5 was subjected to inflation molding in the same manner as in Example 1 to obtain a film.
[0187] In Example 5, the same evaluations were performed as in Example 1. As for the plasticized starch, as shown in Table 1 above, the same evaluation results as in Example 1 were obtained.
[0188] More specifically, the plasticized starch produced in Example 5 was free of bubbles throughout and had a durometer type D hardness of 27. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. In addition, the film surface was free of bleeding and stickiness.
[0189] Example 6
[0190] A plasticized starch was obtained in the same manner as in Example 1, except that 100 parts by mass of phosphate cross-linked tapioca starch, 12 parts by mass of glycerin, 22 parts by mass of ethylene glycol, 27 parts by mass of water, and 1 part by mass of succinic acid were mixed in the mixer as the plasticized starch material, as shown in Table 1. The glycerin, ethylene glycol, water, and succinic acid were mixed in advance before being charged into the mixer.
[0191] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 6") was obtained in the same manner as in Example 1.
[0192] The resin composition of Example 6 was subjected to inflation molding in the same manner as in Example 1 to obtain a film.
[0193] In Example 6, the same evaluations were performed as in Example 1. As for the plasticized starch, as shown in Table 1 above, the same evaluation results as in Example 1 were obtained.
[0194] More specifically, the plasticized starch produced in Example 6 was free of bubbles throughout and had a durometer type D hardness of 25. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. In addition, the film surface was free of bleeding and stickiness.
[0195] Example 7
[0196] A plasticized starch was obtained in the same manner as in Example 1, except that 100 parts by mass of phosphate cross-linked tapioca starch, 34 parts by mass of ethylene glycol, 27 parts by mass of water, and 1 part by mass of succinic acid were mixed in the mixer as the plasticized starch material, as shown in Table 1. The ethylene glycol, the water, and the succinic acid were mixed in advance before being charged into the mixer.
[0197] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 7") was obtained in the same manner as in Example 1.
[0198] The resin composition of Example 7 was subjected to inflation molding in the same manner as in Example 1 to obtain a film.
[0199] In Example 7, the same evaluations were performed as in Example 1. As for the plasticized starch, as shown in Table 1 above, the same evaluation results as in Example 1 were obtained.
[0200] More specifically, the plasticized starch produced in Example 7 was free of bubbles throughout and had a durometer type D hardness of 26. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. In addition, the film surface was free of bleeding and stickiness.
[0201] Example 8
[0202] A plasticized starch was obtained in the same manner as in Example 1, except that 100 parts by mass of phosphate cross-linked tapioca starch, 34 parts by mass of glycerin, and 27 parts by mass of water were mixed in the mixer as the plasticized starch material, as shown in Table 1. The glycerin and the water were mixed in advance before being charged into the mixer.
[0203] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 8") was obtained in the same manner as in Example 1.
[0204] The resin composition of Example 8 was subjected to inflation molding in the same manner as in Example 1 to obtain a film.
[0205] In Example 8, the same evaluations were performed as in Example 1. As for the plasticized starch, as shown in Table 1 above, the same evaluation results as in Example 1 were obtained.
[0206] More specifically, the plasticized starch produced in Example 8 was free of bubbles throughout and had a durometer type D hardness of 24. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. Also, bleeding occurred on the film surface, and the film was sticky.
[0207] Example 9
[0208] As shown in Table 1 above, a plasticized starch was obtained in the same manner as in Example 1, except that 100 parts by mass of corn starch (product name: Showa Corn Starch, Showa Sangyo Co., Ltd.), 34 parts by mass of glycerin, and 27 parts by mass of water were mixed in the mixer as the plasticized starch material. Note that the glycerin and the water were mixed in advance before being charged into the mixer.
[0209] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 9") was obtained in the same manner as in Example 1.
[0210] The resin composition of Example 9 was subjected to inflation molding in the same manner as in Example 1 to obtain a film.
[0211] In Example 9, the same evaluations were performed as in Example 1. As for the plasticized starch, as shown in Table 1 above, the same evaluation results as in Example 1 were obtained.
[0212] More specifically, the plasticized starch produced in Example 9 was free of bubbles throughout and had a durometer type D hardness of 25. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. Also, bleeding occurred on the film surface, and the film was sticky.
[0213] Example 10
[0214] As shown in Table 1 above, a plasticized starch was obtained in the same manner as in Example 1, except that 100 parts by mass of phosphate cross-linked tapioca starch, 12 parts by mass of glycerin, 22 parts by mass of ethylene glycol, and 27 parts by mass of water were mixed in the mixer.
[0215] 70 parts by mass of the plasticized starch, 40 parts by mass of polypropylene (FL6632G, Sumitomo Chemical Co., Ltd.), and 3 parts by mass of a compatibilizer (maleic anhydride modified polypropylene, DuPont Co., Ltd.) were fed into a twin-screw extruder (PCM30, Ikegai Co., Ltd.), and these components were subjected to a kneading treatment. The screw temperature in the kneading treatment was 170°C, and the resin pressure was 4.4 MPa. During the kneading treatment, suction was performed from a vent. Through the kneading treatment, a resin composition (hereinafter also referred to as "resin composition of Example 10") was obtained.
[0216] The resin composition of Example 10 was fed to a sheet extruder (LAB TECH Engineering Co., Ltd.) and subjected to sheet extrusion molding. The sheet extrusion molding was performed at 180 to 200° C. By the sheet extrusion molding, a sheet having a thickness of 0.5 mm (hereinafter, also referred to as the “sheet of Example 10”) was obtained.
[0217] The sheet of Example 10 was also subjected to the same evaluation as that of Example 1. The evaluation results are shown in the above Table 1. As shown in Table 1, the same evaluation results as those of Example 4 were obtained.
[0218] Comparative Example 1
[0219] A plasticized starch was obtained in the same manner as in Example 1, except that 100 parts by mass of corn starch, 25 parts by mass of glycerin, and 31 parts by mass of water were mixed in the mixer as the plasticized starch material, as shown in Table 1. The glycerin and water were mixed in advance before being charged into the mixer.
[0220] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Comparative Example 1") was obtained in the same manner as in Example 1.
[0221] The resin composition of Comparative Example 1 was subjected to inflation molding in the same manner as in Example 1 to obtain a film.
[0222] In Comparative Example 1, the same evaluations were performed as in Example 1. As for the plasticized starch, as shown in Table 1 above, the same evaluation results as in Example 1 were obtained.
[0223] More specifically, the plasticized starch produced in Comparative Example 1 was free of bubbles throughout and had a durometer type D hardness of 26. As for the resin composition, the particle size of the starch particles on the film surface was 50 μm. Also, bleeding occurred on the film surface, and the film was sticky.
[0224] Comparative Example 2
[0225] A plasticized starch was obtained in the same manner as in Example 1, except that 100 parts by mass of the phosphate cross-linked tapioca starch, 34 parts by mass of ethylene glycol, and 27 parts by mass of water were mixed in the mixer as the plasticized starch material, as shown in Table 1. The ethylene glycol and water were mixed in advance before being charged into the mixer.
[0226] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Comparative Example 2") was obtained in the same manner as in Example 1.
[0227] The resin composition of Comparative Example 2 was subjected to inflation molding in the same manner as in Example 1 to obtain a film.
[0228] In Comparative Example 2, the same evaluations were performed as in Example 1. As for the plasticized starch, as shown in Table 1 above, the same evaluation results as in Example 1 were obtained.
[0229] More specifically, the plasticized starch produced in Comparative Example 2 was free of bubbles throughout and had a hardness of 27 in Durometer Type D. As for the resin composition, the particle size of the starch particles on the film surface was 100 μm. In addition, there was no bleeding or stickiness on the film surface.
[0230] An electron microscope photograph of the obtained film is shown in Figure 1(b). As shown in Figure 1(b), in the film containing insufficiently plasticized starch, many starch particles with a particle size of about 100 μm were confirmed on the surface.
[0231] (Summary of evaluation results)
[0232] The starch particle size was as small as 2 μm in Examples 1 to 10. On the other hand, the starch particle sizes in Comparative Examples 1 and 2 were as large as 50 μm and 100 μm, respectively.
[0233] Test Example 2: Production and molding of resin composition containing CNF
[0234] Example 11
[0235] As the plasticized starch material, 100 parts by mass of phosphate cross-linked tapioca starch, 12 parts by mass of glycerin, 22 parts by mass of ethylene glycol, and 27 parts by mass of water in which a 2% suspension of CNF (product name: hardwood, Daio Paper Co., Ltd.) was prepared, and these four components were mixed in a mixer in the same manner as in Example 1 to obtain a mixture. Using this mixture, a kneading process was performed in the same manner as in Example 1 to obtain a plasticized starch containing CNF. The plasticized starch and polypropylene were kneaded in a twin-screw extruder (PCM30, Ikegai Co., Ltd.) to obtain a resin composition (hereinafter also referred to as "resin composition of Example 11").
[0236] The resin composition of Example 11 was fed to an injection molding machine (SH-125, Sumitomo Heavy Industries, Ltd.) and injection molding was performed. The injection molding was performed at 180°C. An injection molded product (based on JIS K 7161) (hereinafter also referred to as "injection molded product of Example 11") was obtained by the injection molding.
[0237] Example 12
[0238] Using the resin composition of Example 1, an injection-molded article (hereinafter also referred to as "injection-molded article of Example 12") was obtained by the above molding method.
[0239] The injection molded products of Example 11 and Example 12 were used to measure tensile properties (maximum stress, elongation at break, and elastic modulus) in accordance with JIS K 7161. In addition, the injection molded products were used to measure Izod impact strength in accordance with JIS K 7110. The measurement results are shown in Table 2 below.
[0240] As shown in Table 2, the injection molded product of Example 11 had a higher tensile strength and a higher tensile elongation than the injection molded product of Example 12. Therefore, it can be seen that the inclusion of CNF can improve the tensile strength and tensile elongation.
[0241] In addition, the injection-molded product of Example 11 had a shorter cooling time during production than the injection-molded product of Example 12, and was superior in terms of production efficiency. Furthermore, CNF is difficult to disperse in thermoplastic resins such as polypropylene, but CNF was well dispersed in the resin composition of Example 11. Therefore, it can be seen that CNF can be well dispersed in a thermoplastic resin by mixing plasticized starch mixed with CNF with a thermoplastic resin.
[0242] [Table 2]
[0243] Test Example 3: Effect of adding organic acids
[0244] (Example 13)
[0245] As shown in Table 3 below, 100 parts by mass of phosphate cross-linked tapioca starch (product name T-1, Matsutani Chemical Industry Co., Ltd.), 7 parts by mass of glycerin, 27 parts by mass of ethylene glycol, 27 parts by mass of water, and 1 part by mass of succinic acid were prepared as the plasticized starch material. These five components were mixed in a mixer. The mixing was performed at room temperature. The glycerin, the ethylene glycol, the water, and the succinic acid were mixed in advance before being put into the mixer. Table 3 below also shows the parts by mass of other plasticized starch material components when the amount of phosphate cross-linked tapioca starch is taken as 100 parts by mass.
[0246] The mixture obtained by this mixing was a powdery mixture. The powdery mixture was treated in the same manner as in Example 1 to obtain a plasticized starch.
[0247] 40 parts by mass of the plasticized starch, 70 parts by mass of polypropylene (PM900C, Sunallomer Co., Ltd.), and 3 parts by mass of a compatibilizer (maleic anhydride modified polyethylene, DuPont Co., Ltd.) were fed into a twin-screw extruder (PCM30, Ikegai Co., Ltd.), and these components were subjected to a kneading treatment. The screw temperature in the kneading treatment was 170°C, and the resin pressure was 4.4 MPa. During the kneading treatment, suction was performed from a vent. Through the kneading treatment, a resin composition (hereinafter also referred to as "resin composition of Example 13") was obtained.
[0248] The resin composition of Example 13 was fed to an inflation molding machine (Placo Corporation, die Φ65, extruder diameter 55 mm, temperature 150°C) and inflation molding was performed. The inflation molding was performed at 150°C to 160°C. A film having a thickness of 40 μm was obtained by the inflation molding.
[0249] In Example 13, the same evaluations as in Example 1 were performed. The evaluation results are shown in Table 3 below. As shown in Table 3, the particle size of the starch particles on the film surface was 2 μm. In addition, there was no bleeding or stickiness on the film surface.
[0250] Example 14
[0251] A plasticized starch was obtained in the same manner as in Example 13, except that 1 part by mass of maleic acid was used instead of succinic acid as the organic acid. Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 14") was obtained in the same manner as in Example 13.
[0252] The resin composition of Example 14 was subjected to inflation molding in the same manner as in Example 13 to obtain a film.
[0253] In Example 14, the same evaluations were performed as in Example 1. The evaluation results are shown in the following Table 3. As shown in Table 3, the same evaluation results as in Example 13 were obtained.
[0254] Example 15
[0255] As shown in Table 3 below, a plasticized starch was obtained in the same manner as in Example 13, except that 100 parts by mass of phosphate cross-linked tapioca starch (product name T-1, Matsutani Chemical Industry Co., Ltd.), 34 parts by mass of glycerin, 27 parts by mass of water, and 3 parts by mass of maleic acid were mixed. Using this plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 15") was obtained in the same manner as in Example 13.
[0256] The resin composition of Example 15 was subjected to inflation molding in the same manner as in Example 13 to obtain a film.
[0257] The same evaluations as in Example 1 were performed in Example 15. The evaluation results are shown in Table 3 below. As shown in Table 3, the particle size of the starch particles on the film surface was 2 μm. However, bleeding occurred on the film surface, and the film was sticky.
[0258] (Example 16)
[0259] As shown in Table 3 below, a plasticized starch was obtained in the same manner as in Example 13, except that 100 parts by mass of phosphate cross-linked tapioca starch (product name T-1, Matsutani Chemical Industry Co., Ltd.), 34 parts by mass of glycerin, and 27 parts by mass of water were mixed. Using this plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 16") was obtained in the same manner as in Example 13.
[0260] The resin composition of Example 16 was subjected to inflation molding in the same manner as in Example 13 to obtain a film.
[0261] In Example 16, the same evaluations as in Example 1 were performed. The evaluation results are shown in Table 3 below. As shown in Table 3, the particle size of the starch particles on the film surface was 2 μm. However, bleeding occurred on the film surface, and the film was sticky.
[0262] Comparative Example 3
[0263] As shown in Table 3 below, 100 parts by mass of phosphate cross-linked tapioca starch (product name T-1, Matsutani Chemical Industry Co., Ltd.), 7 parts by mass of glycerin, 27 parts by mass of ethylene glycol, and 27 parts by mass of water were mixed, and a plasticized starch was obtained in the same manner as in Example 11, except that no organic acid was mixed. Using this plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Comparative Example 3") was obtained in the same manner as in Example 12.
[0264] The resin composition of Comparative Example 3 was subjected to inflation molding in the same manner as in Example 13 to obtain a film.
[0265] In Comparative Example 3, the same evaluations as in Example 1 were performed. The evaluation results are shown in the following Table 3. As shown in Table 3, the particle size of the starch particles on the film surface was 100 μm.
[0266] [Table 3]
[0267] Test Example 3: Production and Evaluation of Laminate
[0268] (Example 17)
[0269] As shown in Table 4 below, 100 parts by mass of phosphate cross-linked tapioca starch (product name T-1, Matsutani Chemical Industry Co., Ltd.), 34 parts by mass of glycerin, and 27 parts by mass of water were mixed to obtain a plasticized starch in the same manner as in Example 1.
[0270] 60 parts by mass of the plasticized starch, 40 parts by mass of polypropylene (PM900C, Sunallomer Co., Ltd.), and 3 parts by mass of a compatibilizer (maleic anhydride modified polypropylene, DuPont Co., Ltd.) were fed into a twin-screw extruder (PCM30, Ikegai Co., Ltd.), and these components were subjected to a kneading treatment. The screw temperature in the kneading treatment was 170°C, and the resin pressure was 4.4 MPa. During the kneading treatment, suction was performed from a vent. Through the kneading treatment, a resin composition (hereinafter also referred to as "resin composition of Example 17") was obtained.
[0271] The resin composition of Example 17 was used to perform sheet extrusion molding in the same manner as in Example 10 to obtain a sheet (hereinafter also referred to as "the sheet of Example 17").
[0272] Both surfaces of the sheet of Example 17 were covered with a polyethylene film having a thickness of 20 μm, and the sheet was vacuum laminated using a vacuum laminator (LM-50X50-S, NCP Corporation). The lamination was performed at 120° C. A laminate having a thickness of 0.5 mm (also referred to as the laminate of Example 17) was obtained by the sheet extrusion molding.
[0273] The laminate of Example 17 was also evaluated in the same manner as in Example 1. The evaluation results are shown in the following Table 4. As shown in Table 4, the starch grains of the sheet obtained from the resin composition of Example 17 observed by SEM were 2 μm in size, and there was no bleeding or stickiness.
[0274] Comparative Example 4
[0275] As shown in Table 4 below, a plasticized starch was obtained in the same manner as in Example 17, except that 100 parts by mass of phosphate cross-linked tapioca starch (product name T-1, Matsutani Chemical Industry Co., Ltd.), 12 parts by mass of glycerin, 22 parts by mass of ethylene glycol, and 27 parts by mass of water were mixed.
[0276] A resin composition (hereinafter also referred to as "resin composition of Comparative Example 10") was obtained using 70 parts by mass of the plasticized starch, 40 parts by mass of polypropylene (PM900C, Sunallomer Co., Ltd.), and 3 parts by mass of a compatibilizer (maleic anhydride modified polypropylene, DuPont Co., Ltd.). Note that no vacuum lamination treatment was performed on both surfaces.
[0277] In Comparative Example 4, the same evaluations as in Example 1 were performed. The evaluation results are shown in Table 4 below. As shown in Table 4, the particle size of the starch particles on the sheet surface was 2 μm. However, slight bleeding occurred on the sheet surface, and there was some stickiness.
[0278] Comparative Example 5
[0279] As shown in Table 4 below, a plasticized starch was obtained in the same manner as in Example 17, except that 100 parts by mass of phosphate cross-linked tapioca starch (product name T-1, Matsutani Chemical Industry Co., Ltd.), 34 parts by mass of glycerin, and 27 parts by mass of water were mixed.
[0280] A resin composition (hereinafter also referred to as "resin composition of Comparative Example 5") was obtained using 60 parts by mass of the plasticized starch, 40 parts by mass of polypropylene (PM900C, Sunallomer Co., Ltd.), and 3 parts by mass of a compatibilizer (maleic anhydride modified polypropylene, DuPont Co., Ltd.). Note that no vacuum lamination treatment was performed on both surfaces.
[0281] In Comparative Example 5, the same evaluation as in Example 1 was performed. The evaluation results are shown in Table 4 below. As shown in Table 4, the particle size of the starch particles on the sheet surface was 2 μm. However, bleeding occurred on the sheet surface, and the sheet was sticky.
[0282] [Table 4]
[0283] Test Example 4: Production and evaluation of nonwoven fabric
[0284] (Example 18)
[0285] The resin composition of Example 1 was supplied to a spunbond molding machine (Japan Steel Works, Ltd.), and the resin composition was discharged from a nozzle hole having a spinning temperature (spinneret temperature) of 200°C to 230°C, a hole diameter D of 0.43 mm, and a land length L of 0.75 mm under the condition of a single hole discharge rate of 13 g / min. The introduction hole located directly above the nozzle hole was a straight hole, and a connection part between the introduction hole and the nozzle hole was tapered. The discharged fibrous resin composition was cooled and solidified by applying cooling air at a temperature of 220°C and a speed of 450 m / min from the outside, and then pulled by a rectangular ejector at a speed of 20 m / min and collected on a moving net to obtain a fiber web.
[0286] The fiber web obtained as described above was thermally bonded at a temperature of 130°C using a pair of upper and lower thermal embossing rolls consisting of a metallic embossing roll with a diamond-shaped pattern engraved on the upper roll and a metallic flat roll on the lower roll, to produce a fiber web with a fiber diameter of 20 μm and a basis weight of 70 g / m. 2 A nonwoven fabric of
[0287] An electron microscope photograph of the surface of the obtained nonwoven fabric is shown in Figure 2. As shown in Figure 2, in the nonwoven fabric formed from a resin composition containing sufficiently plasticized starch, the particle diameter of the starch particles present on the surface of the constituent fibers is about 2 μm, which is sufficiently smaller than the thickness of the fibers.
[0288] Test Example 5: Production and molding of resin composition (example of film or sheet)
[0289] (Example 19)
[0290] A resin composition was produced using polyethylene resin instead of polypropylene resin as the thermoplastic resin. As shown in Table 5 below, 100 parts by mass of phosphate cross-linked tapioca starch (T-1, Matsutani Chemical Industry Co., Ltd.) was prepared as a plasticized starch material, 7 parts by mass of glycerin, 27 parts by mass of ethylene glycol, 27 parts by mass of water, and 1 part by mass of succinic acid were prepared as the resin composition. These five components were mixed in a mixer. The mixing was performed at room temperature. The glycerin, ethylene glycol, water, and succinic acid were mixed in advance before being added to the mixer.
[0291] The mixture obtained by this mixing was a powder mixture.
[0292] The mixture obtained by the above mixing was fed into a twin-screw extruder (PCM30, Ikegai Corporation), and the mixture was subjected to a kneading treatment.
[0293] The cylinder temperature during the kneading process was 110° C. During the kneading process, suction was performed from a vent. After the kneading process, the mixture was extruded from the die of the extruder, and an elongated, roughly cylindrical plasticized starch (master batch) was obtained.
[0294] The plasticized starch was evaluated for the presence or absence of bubbles and durometer hardness according to the same criteria as in Example 1 above.
[0295] The evaluation results are shown in Table 5 below, and the plasticized starch had no bubbles formed throughout. The plasticized starch also had a hardness of 27 in durometer type D.
[0296] 60 parts by mass of the plasticized starch, 40 parts by mass of a linear low density polyethylene resin (LLDPE: Linear Low Density Polyethylene, product name UF641, manufactured by Japan Polyethylene Co., Ltd.), and 3 parts by mass of a compatibilizer (maleic anhydride modified polyethylene, manufactured by DuPont) were fed into a twin-screw extruder (PCM30, manufactured by Ikegai Co., Ltd.), and these components were subjected to a kneading treatment. The screw temperature in the kneading treatment was 170°C, and the resin pressure was 4.4 MPa. During the kneading treatment, suction was performed from a vent. Through the kneading treatment, a resin composition (hereinafter also referred to as "resin composition of Example 19") was obtained.
[0297] The resin composition of Example 19 was fed to an inflation molding machine (Placo Corporation, die Φ65, extruder diameter 55 mm, temperature 150°C) and inflation molding was performed. The inflation molding was performed at 150°C to 160°C. A film with a thickness of 40 µm was obtained by the inflation molding.
[0298] The particle size of the starch particles on the film surface and the presence or absence of bleeding were evaluated according to the same methods and standards as in Example 1 above. The evaluation results are shown in Table 5 below, and an electron microscope photograph of the obtained film is shown in Figure 3(a). As shown in Figure 3(a), the particle size of the starch particles on the film surface was 2 µm. In addition, there was no bleeding on the film surface, and there was no stickiness.
[0299] [Table 5]
[0300] (Example 20)
[0301] As shown in Table 5 above, a plasticized starch was obtained in the same manner as in Example 19, except that 100 parts by mass of phosphate cross-linked tapioca starch, 34 parts by mass of glycerin, and 27 parts by mass of water were mixed in the mixer as the plasticized starch material. The glycerin and the water were mixed in advance before being charged into the mixer.
[0302] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 20") was obtained in the same manner as in Example 19.
[0303] The resin composition of Example 20 was subjected to inflation molding in the same manner as in Example 19 to obtain a film.
[0304] In Example 20, the same evaluations as in Example 19 were performed. The evaluation results are shown in Table 5. As shown in Table 5, the same evaluation results as in Example 19 were obtained for the plasticized starch.
[0305] More specifically, the plasticized starch produced in Example 20 was free of bubbles throughout and had a durometer type D hardness of 27. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. Also, bleeding occurred on the film surface, and the film was sticky.
[0306] Example 21
[0307] As shown in Table 5 above, a plasticized starch was obtained in the same manner as in Example 19, except that 100 parts by mass of corn starch (product name: Showa Corn Starch, Showa Sangyo Co., Ltd.), 34 parts by mass of glycerin, and 27 parts by mass of water were mixed in the mixer as the plasticized starch material. Note that the glycerin and the water were mixed in advance before being charged into the mixer.
[0308] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 21") was obtained in the same manner as in Example 19.
[0309] The resin composition of Example 21 was subjected to inflation molding in the same manner as in Example 19 to obtain a film.
[0310] In Example 21, the same evaluations as in Example 19 were performed. The evaluation results are shown in Table 5. As shown in Table 5, the same evaluation results as in Example 19 were obtained for the plasticized starch.
[0311] More specifically, the plasticized starch produced in Example 21 was free of bubbles throughout and had a hardness of 27 in Durometer Type D. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. Also, bleeding occurred on the film surface, and the film was sticky.
[0312] Example 22
[0313] As shown in Table 5 above, 100 parts by mass of phosphate cross-linked tapioca starch, 7 parts by mass of glycerin, 27 parts by mass of ethylene glycol, and 27 parts by mass of water containing a 2% suspension of CNF (product name: hardwood, Daio Paper Co., Ltd.) were prepared in the mixer as plasticized starch materials, and these four components were mixed in the mixer in the same manner as in Example 19 to obtain a mixture.
[0314] Using this mixture, a kneading treatment was carried out in the same manner as in Example 19 to obtain a plasticized starch containing CNF. Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 22") was obtained in the same manner as in Example 19.
[0315] The resin composition of Example 22 was used to perform inflation molding in the same manner as in Example 19 to obtain a film.
[0316] In Example 22, the same evaluations as in Example 19 were performed. As for the plasticized starch, as shown in Table 5 above, the same evaluation results as in Example 19 were obtained.
[0317] More specifically, the plasticized starch produced in Example 22 was free of bubbles throughout and had a durometer type D hardness of 26. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. In addition, the film surface was free of bleeding and stickiness.
[0318] Comparative Example 6
[0319] As shown in Table 5 above, a plasticized starch was obtained in the same manner as in Example 19, except that 100 parts by mass of phosphate cross-linked tapioca starch, 34 parts by mass of ethylene glycol, and 27 parts by mass of water were mixed in the mixer as the plasticized starch material. The ethylene glycol and the water were mixed in advance before being charged into the mixer.
[0320] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Comparative Example 6") was obtained in the same manner as in Example 19.
[0321] The resin composition of Comparative Example 6 was subjected to inflation molding in the same manner as in Example 19 to obtain a film.
[0322] In Comparative Example 6, the same evaluations as in Example 19 were performed. The evaluation results are shown in Table 5. As shown in Table 5, the same evaluation results as in Example 19 were obtained for the plasticized starch.
[0323] More specifically, the plasticized starch produced in Comparative Example 6 was free of air bubbles throughout and had a durometer type D hardness of 27. However, for the resin composition, the starch particles on the film surface had a large particle diameter of 100 μm. An electron microscope photograph of the obtained film is shown in FIG. 3(b). As shown in FIG. 3(b), the film containing insufficiently plasticized starch had many starch particles with a particle diameter of about 100 μm on the surface.
[0324] Test Example 6: Production and molding of resin composition (example of film or sheet)
[0325] Example 23
[0326] A resin composition was produced using biodegradable resin PBAT (product name Ecoflex (registered trademark), manufactured by BASF Japan Ltd.) as a thermoplastic resin. As shown in Table 6 below, 100 parts by mass of phosphate cross-linked tapioca starch (T-1, Matsutani Chemical Industry Co., Ltd.), 7 parts by mass of glycerin, 27 parts by mass of ethylene glycol, 27 parts by mass of water in which CNF (product name Broadleaf Tree, Daio Paper Co., Ltd.) was suspended at 2% and 1 part by mass of succinic acid were prepared as plasticized starch materials. These five components were mixed in a mixer. The mixing was performed at room temperature. The glycerin, the ethylene glycol, the water in which the CNF was suspended at 2% and the succinic acid were mixed in advance before being put into the mixer.
[0327] The mixture obtained by this mixing was a powder mixture.
[0328] The mixture obtained by the above mixing was fed into a twin-screw extruder (PCM30, Ikegai Corporation), and the mixture was subjected to a kneading treatment.
[0329] The cylinder temperature during the kneading process was 110° C. During the kneading process, suction was performed from a vent. After the kneading process, the mixture was extruded from the die of the extruder, and an elongated, roughly cylindrical plasticized starch (master batch) was obtained.
[0330] The plasticized starch was evaluated for the presence or absence of bubbles and durometer hardness according to the same criteria as in Example 1 above.
[0331] The evaluation results are shown in Table 6 below, and the plasticized starch had no bubbles formed throughout, and had a hardness of 27 in durometer type D.
[0332] 60 parts by mass of the plasticized starch and 40 parts by mass of the biodegradable resin were fed into a twin-screw extruder (PCM30, Ikegai Co., Ltd.), and these components were subjected to a kneading process. The screw temperature in the kneading process was 170°C, and the resin pressure was 4.4 MPa. During the kneading process, suction was performed from a vent. Through the kneading process, a resin composition (hereinafter also referred to as "resin composition of Example 23") was obtained.
[0333] The resin composition of Example 23 was fed to an inflation molding machine (Placo Corporation, die Φ65, extruder diameter 55 mm, temperature 150°C) and inflation molding was performed. The inflation molding was performed at 150°C to 160°C. A film having a thickness of 40 μm was obtained by the inflation molding.
[0334] The particle size of the starch particles on the film surface and the presence or absence of bleeding were evaluated according to the same method and criteria as in Example 1. The evaluation results are shown in Table 6 below, and the particle size of the starch particles on the film surface was 2 μm. In addition, there was no bleeding or stickiness on the film surface.
[0335] [Table 6]
[0336] (Example 24)
[0337] As shown in Table 6 above, plasticized starch was obtained in the same manner as in Example 23, except that 27 parts by mass of water was mixed in the mixer instead of the water in which a 2% suspension of CNF (product name: hardwood, Daio Paper Co., Ltd.) was suspended. Note that the glycerin, ethylene glycol, water, and succinic acid were mixed in advance before being put into the mixer.
[0338] Using the plasticized starch, a resin composition (hereinafter also referred to as "resin composition of Example 24") was obtained in the same manner as in Example 23.
[0339] The resin composition of Example 24 was subjected to inflation molding in the same manner as in Example 23 to obtain a film.
[0340] In Example 24, the same evaluations as in Example 23 were performed. The evaluation results are shown in Table 6. As shown in Table 6, the same evaluation results as in Example 23 were obtained for the plasticized starch.
[0341] More specifically, the plasticized starch produced in Example 24 was free of bubbles throughout and had a durometer type D hardness of 27. As for the resin composition, the particle size of the starch particles on the film surface was 2 μm. In addition, the film surface was free of bleeding and stickiness.
[0342] Test Example 7: Production and molding of resin composition (example of deodorizing sheet)
[0343] (Example 25)
[0344] A resin composition was produced using polyethylene resin as the thermoplastic resin. As shown in Table 7 below, 100 parts by mass of phosphate cross-linked tapioca starch (T-1, Matsutani Chemical Industry Co., Ltd.), 34 parts by mass of glycerin, 27 parts by mass of water, and 2 parts by mass of deodorant*1 (Fabrese, manufactured by P&G) were prepared as the plasticized starch material. These four components were mixed in a mixer. The mixing was performed at room temperature. The glycerin, the water, and the deodorant*1 were mixed in advance before being put into the mixer.
[0345] The mixture obtained by this mixing was a powder mixture.
[0346] The mixture obtained by the above mixing was fed into a twin-screw extruder (PCM30, Ikegai Corporation), and the mixture was subjected to a kneading treatment.
[0347] The cylinder temperature during the kneading process was 110° C. During the kneading process, suction was performed from a vent. After the kneading process, the mixture was extruded from the die of the extruder, and an elongated, roughly cylindrical plasticized starch (master batch) was obtained.
[0348] 30 parts by mass of the plasticized starch, 70 parts by mass of a linear low density polyethylene resin (LLDPE: Linear Low Density Polyethylene, product name UF641, manufactured by Japan Polyethylene Co., Ltd.), and 3 parts by mass of a compatibilizer (maleic anhydride modified polyethylene, manufactured by DuPont) were fed into a twin-screw extruder (PCM30, manufactured by Ikegai Co., Ltd.), and these components were subjected to a kneading treatment. The screw temperature in the kneading treatment was 170°C, and the resin pressure was 4.4 MPa. During the kneading treatment, suction was performed from a vent. Through the kneading treatment, a resin composition (hereinafter also referred to as "resin composition of Example 25") was obtained.
[0349] The resin composition was evaluated for its aromatic property.
[0350] <Aromatic properties of resin composition> The aromatic properties of the resin compositions were evaluated sensorily according to the following method and criteria. The resin composition of Example 25 was fed to an inflation molding machine (Placo Corporation, die Φ65, extruder diameter 55 mm, temperature 150°C) and inflation molding was performed. The inflation molding was performed at 150°C to 160°C. A tubular film having a thickness of 30 to 40 μm was obtained by the inflation molding. One end of the tube was tied to form a bag. A filter paper having a diameter of 10 cm was placed with 2 to 3 drops of a skatole / indole-containing fragrance in it, and the other end of the tube that was not tied was tied. A panel of seven people smelled the outside of the bag to confirm whether the fragrance of the deodorant remained. The fragrance of the resin composition was evaluated by a sensory evaluation according to the following criteria. A: The smell of the deodorant remains strong and fragrant. B: A faint odor of deodorant remains, with a slight fragrance C: No deodorant scent remains, no fragrance
[0351] The evaluation results are shown in Table 7 below, and the resin composition had a fragrance.
[0352] [Table 7]
[0353] The materials used in this test example are as follows: Deodorizer*1: Febreze (commercial product), made by P&G Deodorant*2: Deodorant family commercial product, manufactured by Universe Development Co., Ltd.
[0354] (Example 26)
[0355] A film was produced in the same manner as in Example 25, except that deodorant *2 (Shoshu Kazoku, manufactured by Universe Development Co., Ltd.) was used instead of deodorant *1 (Fabrese, manufactured by P&G), and the aromaticity of the resin composition was evaluated. As shown in Table 7 above, the resin composition had an aromatic odor.
[0356] Example 27
[0357] A film was produced in the same manner as in Example 25, except that 34 parts by mass of ethylene glycol and 1 part by mass of maleic acid were added instead of adding glycerin, and the aromaticity of the resin composition was evaluated. As shown in Table 7 above, the resin composition had an aromatic odor.
[0358] (Example 28)
[0359] A film was produced in the same manner as in Example 27, except that deodorant *2 (Shoshu Kazoku, manufactured by Universe Development Co., Ltd.) was used instead of deodorant *1 (Fabrese, manufactured by P&G), and the aromaticity of the resin composition was evaluated. As shown in Table 7 above, the resin composition had an aromatic odor.
[0360] Comparative Example 7
[0361] A film was produced in the same manner as in Example 25, except that the deodorant*1 was not blended, and the aromatic properties of the resin composition were evaluated. As shown in Table 7 above, the resin composition did not retain the scent of the deodorant.
[0362] Comparative Example 8
[0363] A film was produced in the same manner as in Example 25, except that 100 parts by mass of corn starch (product name: Showa Corn Starch, Showa Sangyo Co., Ltd.) was blended as the plasticized starch material and no deodorant*1 was blended, and the aromatic properties of the resin composition were evaluated. As shown in Table 7 above, the resin composition did not retain the scent of the deodorant.
[0364] (Example 29)
[0365] As shown in Table 8 below, 100 parts by mass of phosphate cross-linked tapioca starch (product name T-1, Matsutani Chemical Industry Co., Ltd.), 34 parts by mass of ethylene glycol, 27 parts by mass of water, 1 part by mass of maleic acid, and 2 parts by mass of deodorant*1 (Fabrese, manufactured by P&G) were prepared as the plasticized starch material. These five components were mixed in a mixer. The mixing was performed at room temperature. The ethylene glycol, water, maleic acid, and deodorant*1 were mixed in advance before being put into the mixer. Table 8 below shows the parts by mass of other plasticized starch material components when the amount of phosphate cross-linked tapioca starch is 100 parts by mass.
[0366] The mixture obtained by this mixing was a powdery mixture. The powdery mixture was treated in the same manner as in Example 1 to obtain a plasticized starch.
[0367] 30 parts by mass of the plasticized starch, 70 parts by mass of polypropylene (PM900C, Sunallomer Co., Ltd.), and 3 parts by mass of a compatibilizer (maleic anhydride modified polyethylene, DuPont Co., Ltd.) were fed into a twin-screw extruder (PCM30, Ikegai Co., Ltd.), and these components were subjected to a kneading treatment. The screw temperature in the kneading treatment was 170°C, and the resin pressure was 4.4 MPa. During the kneading treatment, suction was performed from a vent. Through the kneading treatment, a resin composition (hereinafter also referred to as "resin composition of Example 29") was obtained.
[0368] The resin composition of Example 29 was fed to an inflation molding machine (Placo Corporation, die Φ65, extruder diameter 55 mm, temperature 150°C) and inflation molding was carried out. The inflation molding was carried out at 150°C to 160°C. A tubular film having a thickness of 30 to 40 μm was obtained by the inflation molding.
[0369] In Example 29, the same evaluations as in Example 25 were performed. The evaluation results are shown in the following Table 8. As shown in Table 8, the resin composition had a fragrance.
[0370] [Table 8]
[0371] The materials used in this test example were the same as those used in Table 7.
[0372] (Example 30)
[0373] A film was produced in the same manner as in Example 29, except that deodorant *2 was used instead of deodorant *1, and the fragrance of the resin composition was evaluated. As shown in Table 8 above, the resin composition had a fragrance.
[0374] (Example 31)
[0375] A film was produced in the same manner as in Example 30, except that 1 part by mass of the deodorant*2 was added, and the aromatic property of the resin composition was evaluated. As shown in Table 8 above, the resin composition had an aromatic odor.
[0376] Comparative Example 9
[0377] A film was produced in the same manner as in Example 29, except that the deodorant *1 was not blended, and the fragrance of the resin composition was evaluated. As shown in Table 8 above, the resin composition had no fragrance.
[0378] Comparative Example 10
[0379] A film was produced in the same manner as in Example 29, except that 100 parts by mass of corn starch (product name: Showa Corn Starch, Showa Sangyo Co., Ltd.) was blended as the plasticized starch material, 34 parts by mass of glycerin was blended instead of ethylene glycol, and maleic acid and deodorant*1 were not blended, and the aromaticity of the resin composition was evaluated. As shown in Table 8 above, the resin composition had no aromatic odor.
[0380] Example 32
[0381] A resin composition was produced using biodegradable resin PBAT (product name Ecoflex (registered trademark), manufactured by BASF Japan Ltd.) as the thermoplastic resin. As shown in Table 9 below, 100 parts by mass of phosphate cross-linked tapioca starch (T-1, Matsutani Chemical Industry Co., Ltd.), 34 parts by mass of glycerin, 27 parts by mass of water, and 2 parts by mass of deodorant*1 (Fabrese, manufactured by P&G) were prepared as the plasticized starch material. These four components were mixed in a mixer. The mixing was performed at room temperature. The glycerin, the water, and the deodorant*1 were mixed in advance before being added to the mixer.
[0382] The mixture obtained by this mixing was a powder mixture.
[0383] The mixture obtained by the above mixing was fed into a twin-screw extruder (PCM30, Ikegai Corporation), and the mixture was subjected to a kneading treatment.
[0384] The cylinder temperature during the kneading process was 110° C. During the kneading process, suction was performed from a vent. After the kneading process, the mixture was extruded from the die of the extruder, and an elongated, roughly cylindrical plasticized starch (master batch) was obtained.
[0385] 30 parts by mass of the plasticized starch and 70 parts by mass of the biodegradable resin were fed into a twin-screw extruder (PCM30, Ikegai Co., Ltd.), and these components were subjected to a kneading process. The screw temperature in the kneading process was 170°C, and the resin pressure was 4.4 MPa. During the kneading process, suction was performed from a vent. Through the kneading process, a resin composition (hereinafter also referred to as "resin composition of Example 32") was obtained.
[0386] The resin composition of Example 32 was fed to an inflation molding machine (Placo Corporation, die Φ65, extruder diameter 55 mm, temperature 150°C) and inflation molding was performed. The inflation molding was performed at 150°C to 160°C. A tubular film having a thickness of 30 to 40 μm was produced by the inflation molding, and the aromaticity of the resin composition was evaluated. The evaluation results are shown in Table 9 below, and the resin composition had an aromatic odor.
[0387] [Table 9]
[0388] The materials used in this test example were the same as those used in Table 8.
[0389] (Example 33)
[0390] A film was produced in the same manner as in Example 32, except that deodorant *2 was used instead of deodorant *1, and the fragrance of the resin composition was evaluated. As shown in Table 9 above, the resin composition had a fragrance.
[0391] (Example 34)
[0392] A film was produced in the same manner as in Example 32, except that 34 parts by mass of ethylene glycol was added instead of glycerin, and 1 part by mass of maleic acid was further added, and the aromaticity of the resin composition was evaluated. As shown in Table 9 above, the resin composition had an aromatic odor.
[0393] (Example 35)
[0394] A film was produced in the same manner as in Example 34, except that deodorant *2 was used instead of deodorant *1, and the fragrance of the resin composition was evaluated. As shown in Table 9 above, the resin composition had a fragrance.
[0395] Comparative Example 11
[0396] A film was produced in the same manner as in Example 32, except that the deodorant *1 was not blended, and the fragrance of the resin composition was evaluated. As shown in Table 9 above, the resin composition had no fragrance.
[0397] Comparative Example 12
[0398] A film was produced in the same manner as in Example 35, except that the deodorant *1 was not blended, and the fragrance of the resin composition was evaluated. As shown in Table 9 above, the resin composition had no fragrance.
[0399] Comparative Example 13
[0400] A film was produced in the same manner as in Example 32, except that 100 parts by mass of corn starch (product name: Showa Corn Starch, Showa Sangyo Co., Ltd.) was blended as the plasticized starch material and no deodorant*1 was blended, and the aromaticity of the resin composition was evaluated. As shown in Table 9 above, the resin composition had no aromaticity.
Claims
1. a plasticized starch material and a thermoplastic resin; the plasticized starch material comprises starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, water (excluding the equilibrium moisture contained in the starch), and a carboxylic acid having two or more carboxyl groups; and, The particle size of the starch measured by a secondary electron image using a scanning electron microscope is 2 μm or less. Resin composition.
2. The resin composition according to claim 1 , wherein the polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature includes at least one polyhydric alcohol.
3. The resin composition according to claim 2 , wherein the polyhydric alcohol comprises at least one of ethylene glycol and propylene glycol.
4. The resin composition according to any one of claims 1 to 3, wherein the plasticized starch material comprises a plasticized starch or a plasticized modified starch.
5. The resin composition according to any one of claims 1 to 4, wherein the thermoplastic resin is a polyolefin-based resin, a polyester-based resin, a polystyrene-based resin, or a mixture of these resins.
6. The resin composition according to any one of claims 1 to 5, further comprising cellulose nanofibers.
7. The resin composition according to any one of claims 1 to 6, which is formed into the shape of a film, a sheet, or a nonwoven fabric.
8. The resin composition according to any one of claims 1 to 6, which is formed into a film or sheet shape, and the surface of the film or sheet is covered with a membrane to form a laminate.
9. a first mixing step of mixing starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, water (excluding the equilibrium moisture contained in the starch), and a carboxylic acid having two or more carboxyl groups; a plasticized starch preparation step of plasticizing the starch by heating the mixture obtained in the first mixing step to prepare a plasticized starch; and A method for producing a resin composition, comprising a second mixing step of mixing the plasticized starch and a thermoplastic resin to obtain a resin composition containing starch having a particle diameter of 2 μm or less as measured by a secondary electron image using a scanning electron microscope.
10. A mixing step of mixing starch, a polar organic compound capable of gelatinizing or plasticizing starch at a temperature higher than room temperature, water (excluding the equilibrium moisture contained in the starch), a carboxylic acid having two or more carboxyl groups, and a thermoplastic resin; A method for producing a resin composition, comprising: a heating step of heating the mixture obtained in the mixing step to plasticize the starch and obtain starch having a particle diameter of 2 μm or less as measured by a secondary electron image using a scanning electron microscope.
11. The resin composition according to claim 1 , further comprising a functional agent.
12. The resin composition according to claim 11, wherein the functional agent is at least one selected from the group consisting of an antibacterial agent, a deodorant, and a deodorant alone or in combination.
13. The method for producing a resin composition according to claim 9 , further comprising mixing a functional agent in the first mixing step.
14. The method for producing a resin composition according to claim 10 , further comprising mixing a functional agent in the mixing step.
Citation Information
Patent Citations
Starch-based biodegradable article and manufacturing method thereof
JP1991505232A
Composition of starch-based biodegradable resin / Waste paper complex and molded product thereof
JP2000239440A
Biodegradable polymer composition consisting of starch and thermoplastic polymer
JP2000509427A
Thermoplastically processable starch or starch derivative-polymer mixture
JP2000516653A
Starch-based thermoplastic mixture comprising at least one cationic starch and at least one anionic starch, use of said mixture and process for producing said mixture
JP2002534534A